Endogenous 6-phospho-β-glucosidase overexpression in Lactiplantibacillus plantarum modulates selective enrichment of bioactive and volatile metabolites in black tea extract - Yao-Zeng Zhang; Zhi-Peng Cheng; Pei-Yi Feng; Xin-Xin Liu; Rui-Shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (Food Microbiology, 2026)

Polystyrene nanoparticles impair endometrial decidualization in early pregnant mice via oxidative stress-driven autophagy suppression and ferroptosis induction - Li-Qing Wang; Qian-Feng Qiao; Huang-Nian You; Yi-bin Zheng; Xiao-Mei Wu; Wen-Jie Yu; Zeng Liu; Wen-Juan Song; Lin-Hong Zhang; Jia-Rui Hu; Xin-Yu Mao; Yong-Jiang Zhou (Food and Chemical Toxicology, 2026)

Vessel-derived metal ions catalyze the accumulation of representative aging markers in multi-round Jiang-flavor base liquor - Wei Zhang; Shi-Yi Wang; Man-Si Niu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Rong-Kun Tu; Song-Tao Wang; Cai-Hong Shen; Jun-Jie Jia; Xiao-Juan Zhang; Zheng-Hong Xu (Food Research International, 2026)

Spatiotemporal temperature trajectories underpin predictive modeling of microbial succession in single-batch high-temperature daqu solid-state fermentation - Jun-Jie Fu; Wei Shi; Han-Jun Shen; Sheng-Bing Yang; Bo Ren; Rong-Ze Ren; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Song-Tao Wang; Su-Yi Zhang; et al. (Bioresource Technology, 2026)

Accumulation of hydrophobic bile acids mediates chronic heat stress-induced liver-gut axis injury in spotted seabass (Lateolabrax maculatus) - Fan-bo Yang; Xue-shan Li; Kai Song; Ling Wang; Rui-juan Ma; Kang-le Lu; Chun-xiao Zhang (Aquaculture, 2026)

Integrated transcriptomic and metabolomic analyses reveal the involvement of AtGASA1 and AtGASA4 in salicylic acid pathway-associated immune responses in Arabidopsis - Jian-Bo Song; Ya-Ru Li; Zi-Xin Zhao; Xian-Zhi Zuo; Cai-Feng Wang; Min Huang; Shu-Fan Liu; Yu-Fan Chen; Wen-Qian Song; Lin Wang; Ying-Juan Wang; Xuan Huang (Plant Science, 2026)

Integrating ecological networks and metagenomics to decipher core microbial drivers of organic acid metabolism during heaped fermentation of sauce-flavor Baijiu - Hong-Yan Zhang; Ting-Cai Huang; Li-Juan Chai; Wei Shi; Yang-Xue He; Zhen-Ming Lu; Xiao-Juan Zhang; Song-Tao Wang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (Food Research International, 2026)

Decoding the thermocyclic solar-driven fermentation: Multi-omics insights into microbial and metabolic dynamics of traditional Chishui river basin soy sauce - Wei-Qin Deng; Zhen-Ming Lu; Xiong-Bo Li; Zhi-Yi Fan; Ting Li; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Qi-Sheng Zhang; Jin-Song Shi; Gong Chen; Zheng-Hong Xu (Food Chemistry, 2026)

Modeling and analysis of the effect of dissolved oxygen on the dynamics of Plankton system in shallow lakes - Juan Li; Yongzhong Song; Huaiping Zhu (Mathematical Biosciences, 2026)

Microbial and environmental determinants of 1-propanol biosynthesis in Jiang-flavor Baijiu fermentation - Wei-Tao Zhai; Han Zhao; Li-Juan Chai; Wei Zhang; Xiao-Juan Zhang; Zhen-Ming Lu; Chuan-Qiang Gao; Guan-Ru Si; Wen-Qing Zhang; Song-Tao Wang; Cai-Hong Shen; Zheng-Hong Xu (Food Microbiology, 2026)

Concentration-dependent variation in carbon allocation and microbial assembly in chain elongation microbiota: Comparative effects of acetate, ethanol, and lactate - Ya-Ning Song; Li-Juan Chai; Ling Ao; Jun-Lan Mei; Yu-Long Li; Zhen-Ming Lu; Xiao-Juan Zhang; Song-Tao Wang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (Bioresource Technology, 2026)

Removal of antibiotics by an oleaginous green microalga Chromochloris zofingiensis under photoautotrophic, heterotrophic and mixotrophic conditions - Kai-Lu Cao; Juan Peng; Meng-Zhen Li; Lin-Yun Liao; Zi-Wen Song; Hong-Zhi He; Jun Zhao (Algal Research, 2026)

Ginsenoside compound K inhibits migration and invasion of melanoma cells by regulating EMT via the IL-6/STAT3 signaling pathway - Xueyan Sun; Qiushi Li; Yuankuan Jiang; Zhe Hou; Qingshan Li; Tingting Xu; Juan Song (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Acute topical menthol application and exercise performance: A systematic review and meta-analysis of perceptual and physiological responses - Yong Wang; Xiaohan Fan; Hansen Li; Xing Zhang; Mingyue Yin; Kai Xu; Yuming Zhong; Yilin Zhang; Juan Cui; Tianyu Song; Ping Liu; Hengzhi Deng (Journal of Thermal Biology, 2026)

Enhanced glyphosate biodegradation by heavy metal-tolerant microbial consortium QLBS in co-contaminated environment: Kinetics and metabolic pathways - Zeren Li; Mengyi Chen; Ziye Chen; Wen-Juan Chen; Mingqiu Liu; Guiling Si; Haoran Song; Huijie Zhou; Zhenyu Zhang; Bin Liang; Sandhya Mishra; Mohamed A. Ghorab; et al. (Journal of Cleaner Production, 2026)

Ni-Nb-P composite catalyst for efficient Hydrodeoxygenation of lignin derivatives - Chunxia Song; Naidong Li; Hanyu Li; Shaoyun Shan; Yunfei Zhi; Xianghong Li; Fashe Li; Juan Xu (Fuel, 2026)

Deciphering Qu-aroma in Nongxiangxing baijiu via a customized aroma base solution - Sheng-Bing Yang; Zhen-Ming Lu; Jia-Nan Hu; Ting-Yao Tu; Man-Si Niu; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Song-Tao Wang; Su-Yi Zhang; Cai-Hong Shen; Jin-Song Shi; et al. (Food Research International, 2026)

Proteomic comparison of human neural cell-derived extracellular vesicles and parental cells from Alzheimer’s disease and cognitively normal individuals - Jia-Yan Xin; Jie Liu; Hao-Min Dong; Hai-Lun Yu; Zhong-Song Xiao; Jian-Ni Hu; Qiu Jiang; Yu-Peng Zhu; Lin Feng; Yun Feng; Yu-Juan Jia; Zi-Yu Yuan; et al. (Science China Life Sciences, 2026)

Advances in Alzheimer’s disease: mechanistic insights and therapeutic targets - Yu-Juan Jia; Yi-Jun Ge; Bowei Li; Ying Yang; Huaqiu Chen; Jie Liu; Jun-Hong Guo; Jin-Tai Yu; Ke-Qiang Ye; Jian-Zhi Wang; Weihong Song; Yan-Jiang Wang (Science China Life Sciences, 2026)

High-performance quantum interconnect between bosonic modules beyond transmission loss constraints - Hongwei Huang; Jie Zhou; Weizhou Cai; Weiting Wang; Yilong Zhou; Yunlai Zhu; Ziyue Hua; Yifang Xu; Lida Sun; Juan Song; Tang Su; Ming Li; et al. (Science Bulletin, 2026)

Hexavalent chromium inhibits testosterone synthesis in bovine testicular leydig cells through mitochondrial damage via BNIP3 - Hongxia Li; Jia Liu; Liwei Huang; Yu Cheng; Guoqing Zhao; Xiaolong Pan; Lijuan Huang; Pengkang Song; Le Zhao; Xuanqi Yu; Juan Xiong; Qing Tian; et al. (Reproductive Biology, 2026)

Copper isotope perspective on sulfide-silicate liquid immiscibility - Li-Juan Zhu; Lie-Meng Chen; Peter C. Lightfoot; Sheng-Ao Liu; Dan-Dan Li; Song-Yue Yu; Rui-Zhong Hu (Geochimica et Cosmochimica Acta, 2026)

Magnesium isotope geochemistry in continental flood basalts: implications for mantle source heterogeneity - Sakine Moradi; Lie-Meng Chen; Peter C. Lightfoot; Kang-Jun Huang; Qiao Su; Song-Yue Yu; Li-Juan Zhu; Rui-Zhong Hu (Geochimica et Cosmochimica Acta, 2026)

Morphology-driven catalytic performance of H-ZSM-5 in benzene alkylation with syngas - Qicheng Li; Xihu Zhao; Xiaobo Song; Juan Dong; Zhitong Zhao; Pan Hao; Qi Shi; Xuekuan Li (Fuel, 2026)

Cultivar-specific divergence in volatile aroma profiles of heat-stressed grapes uncovered via GC×GC-TOFMS - Chenlu Du; Xinrui Liu; Minying Liu; Mingzheng Han; Zhen Zhang; Yuanyuan Xu; Yue Song; Yuanxu Teng; Dongying Fan; Junpeng Li; Lujia Wang; Juan He; et al. (Food Chemistry, 2026)

Dietary creatine supplementation promoted growth performance, muscle growth and protein deposition in red swamp crayfish (Procambarus clarkii) fed with all-plant-protein diets - Xinyuan Li; Changchun Song; Shouqi Xie; Min Wan; Yangyang Liu; Chenxi Wang; Guogen Su; Feng Huang; Juan Tian (Aquaculture, 2026)

Effects of Iodine Nutritional Status on Thyroid Proliferation of SD Rat - Junshuai Cheng; Zifan Gao; Yuan Zhao; Qiuyi Song; Yu Wang; Tingting Xu; Kai Lv; Yanlei Li; Wanqi Zhang; Juan Liu; Long Tan (Biological Trace Element Research, 2026)

DCDGNet: Dual-frequency cross-feature diffusion GAN for single fusion sonar image generation in exposed subsea pipeline inspection - Jingyao Zhang; Xuerong Cui; Song Dai; Juan Li; Lei Li (Marine Pollution Bulletin, 2026)

Two subtropical mycorrhizal tree species differ in contributions to soil carbon pools under drought - Juan Wang; Mengyang Deng; Yanyan Bian; Yi Li; Sarita Keski-Saari; Qingpei Yang; Jun Liu; Fenggang Luan; Qingni Song; Xin Xiong; Dan Xi; Xiong Fang (Plant and Soil, 2026)

Synthesis of polycyclic High-Density jet fuel from β-Pinene and Lignocellulose-Derived aromatic aldehydes - Naidong Li; Chunxia Song; Shaoyun Shan; Hongfei Gao; Xianghong Li; Juan Xu (Fuel, 2026)

Synthesis strategies, characterization techniques, and prospects of defect-engineered single-atom catalysts for electrocatalysis - Min Yang; Mingyuan Pang; Haohao Zhang; Juan An; Zifan Wang; Jiajia Ye; Zhen Kong; Yuanyuan Du; Jiayu Qu; Chenxi Li; Jibin Song (Fuel, 2026)

ESIRA, a novel framework integrating efficacy and safety for evaluating first-line treatments in advanced hepatocellular carcinoma - Hai-Long Li; Hui Zhou; Yi-Yang Zhang; Jin-Ting Lai; Zhen-Zhong Zhou; Jing-Yi Huang; Song-Bin Guo; Yu Wang; Wei-Juan Huang; Xiao-Peng Tian (Science China Life Sciences, 2026)

PRDX6 as a Ferroptosis-Related Hub Gene in the Entorhinal Cortex of Alzheimer’s Disease: A Multidimensional Bioinformatics and Experimental Validation Study - Xiaolin Li; Ziteng Man; Tiantian Cheng; Juan Song; Yanan Bao; Yu Lin; Hongyan Yang (Journal of Molecular Neuroscience, 2026)

Characteristics of organic phosphorus in sediments from lakes: Regeneration for eutrophication or a geological record in the Anthropocene? - Xiaojie Bing; Yuanrong Zhu; Huihui Ma; Juan Jiang; Yue Li; Qihao Zhou; Yidan Tan; Yuyao Wang; Qingshuai Song; Sailan He; Fengchang Wu (Water Research, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Ultrasound-driven structural remodeling of coconut protein isolate: mechanisms of aggregation control and gel network reinforcement - Mi Tian; Maoxia Li; Xuezhen Liu; Maye Li; Yuanyang Song; Juan Du; Huan Wang; Lianzhou Jiang; Tian Tian; Zhaoxian Huang (Food Chemistry, 2026)

Lactic acid modulates empty-cup aroma persistence in Baijiu via molecular interaction mechanisms: a case study of strong-aroma and soy-sauce-aroma Baijiu - Qing-Ru Liu; Shun-Hua Zhang; Xiao-Juan Zhang; Zheng-Juan Zhu; Ru-Yi Li; Song-Tao Wang; Jin-Song Shi; Su-Yi Zhang; Cai-Hong Shen; Guan-Yu Fang; Qing-Qing Liu; Yong-Jun Yuan; et al. (Food Chemistry, 2026)

Regulation of grain protein content by the amino acid permease gene OsAAP4 in rice - Ming-Xin Li; Feng-Lin Huang; Jin-Hong Lin; Jia-Yi Qu; Guo-Feng Wan; Gen-Cai Song; Jing Zhao; Yan Peng; Zhen-Ning Teng; Ling Liu; Cheng Zheng; Hou-Xiong Wu; et al. (Theoretical and Applied Genetics, 2026)

Characterization and production optimization of genistein by the novel endophytic fungus Aspergillus sydowii J11 isolated from pigeon pea (Cajanus cajan) and its antibacterial and antioxidant properties - Bin-bin Li; Xuexia Gao; Min Lv; Wen-juan Ning; Jing-tao Liang; Xin-yu Fan; Xin-ming Lv; Jin-feng Song; Xiao-han Yuan; Cheng-bo Gu (Biotechnology Letters, 2026)

Development of a high-throughput LLE-UPLC-QqQ-MS/MS method and comprehensive profiling of urinary steroid hormones in Chinese elderly adults - Xiao Ma; Huimin Ren; Li Zhao; Xiaojie Guo; Jiran Zhang; Juan Liu; Xiaona Wang; Mengyao Wang; Yifu Lu; Shilu Tong; Hongyang Cui; Hong Chang; et al. (Analytica Chimica Acta, 2026)

Innovative strategies: using nontraditional chemical methods to enhance the application of biocontrol agents in post-harvest preservation of agricultural products - Jing He; Zhuyin Liu; Guijing Li; Juan Zhao; Zibo Song; Yongli Jiang; Yishu Deng; Junjie Yi (Critical Reviews in Food Science and Nutrition, 2026)

Ocean Heat Content Sets Another Record in 2025 - Yuying Pan; Lijing Cheng; John Abraham; Kevin E. Trenberth; James Reagan; Juan Du; Zhankun Wang; Andrea Storto; Karina Von Schuckmann; Yujing Zhu; Michael E. Mann; Jiang Zhu; et al. (Advances in Atmospheric Sciences, 2026)
Global ocean warming continued unabated in 2025 in response to increased greenhouse gas concentrations and recent reductions in sulfate aerosols, reflecting the long-term accumulation of heat within the climate system, with conditions evolving toward La Niña during the year. In 2025, global upper 2000 m ocean heat content (OHC) increased by ∼23 ± 8 ZJ relative to 2024 according to IAP/CAS estimates. CIGAR-RT, and Copernicus Marine data confirm the continued ocean heat gain. Regionally, about 33% of the global ocean area ranked among its historical (1958–2025) top three warmest conditions, while about 57% fell within the top five, including the tropical and South Atlantic Ocean, Mediterranean Sea, North Indian Ocean, and Southern Oceans, underscoring the broad ocean warming across basins. Multiple datasets consistently indicate ocean warming, as measured by 0–2000 m OHC, increased from 0.14 ± 0.03 W m −2 (10 yr) −1 during 1960–2025 to 0.32 ± 0.14 W m −2 (10 yr) −1 during 2005–2025 (IAP/CAS), the latter being consistent with EEI (Earth’s Energy Imbalance) estimates within uncertainties. In contrast, the global annual mean sea surface temperature (SST) in 2025 was 0.49°C above the 1981–2010 baseline and 0.12 ± 0.03°C lower than in 2024 (IAP/CAS; similar in CMA-SST, FY3 MWRI SST, ERSSTv5 and Copernicus Marine data), consistent with the development of La Niña conditions, but still ranking as the third-warmest year on record.

A fluorescent probe based solid-state fluorophore for the detection of N2H4 and its application in environmental samples - Cong-Ping Cao; Qian Song; Chu-Yu-Hui Peng; Shuang-Xian Li; Guo-Jiang Mao; Juan Ouyang; Liufang Hu; Yongfei Li; Chun-Yan Li (Journal of Hazardous Materials, 2026)

Integrated Necroptosis Within Programmed Cell Death in Traumatic Brain Injury - Ao Li; Tian-Wei Pei; Hao Qi; Juan Fang; Zhi-Song Ding; Yu Wang; Yu-Qiang Zhang; Tao Chen (Molecular Neurobiology, 2026)

Downregulation of NFIA facilitates glycolysis, histone lactylation, and activation of the FN1–integrin α5β1 pathway in pancreatic cancer - Xi Zhang; Yang Liu; Xiaoming Liu; Juan Tan; Lehong Yuan; Weijie Wu; Xiaoyan Li; Pan Xi; Guoyin Li; Zewen Song (Apoptosis, 2026)

Toonasinetins A and B, two new compounds from the branches and leaves of Toona sinensis - Nai-Dong Li; Cheng-Shan Wei; Chun-Xia Song; Chun-Jiang Du; Juan Xu (Phytochemistry Letters, 2025)

Joint influences of ENSO and East Asian winter monsoon on the Hadley circulation in the Asian monsoon domain - Mengying Du; Yan Li; Juan Feng; Qi Wen; Wenjun Song; Zhilan Wang (Global and Planetary Change, 2025)

Multi-system toxicity of lead (Pb) in Procambarus clarkii: Integrated analysis of tissue damage, immune dysfunction, oxidative stress, and microbial dysbiosis via multi-omics approaches - Lang Zhang; Ziwei Song; Qiuying Qin; Li He; Juan Tian; Yali Yu; Yingchun Mu; Liqi Zhong; Zongbin Cui; Jinhua Gan (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

NADPH oxidase-mimicking nanozyme for disulfidptosis-induction strategy to amplify cuproptosis in cancer therapy - Juan Ruan; Chen Li; Yu Wang; Chunhui Wang; Xinda Yang; Chuansheng Xu; Yan Gao; Song Hu; Shuo Shi (Chemical Engineering Journal, 2025)

Synthesis of d-p orbital hybridised ultra-thin high-entropy oxide nanosheets for efficient oxygen evolution reaction - Xiaoyin Li; Chuncheng Xu; Lulu Suo; Juan Wang; Deliang Zhang; Miaomiao Xing; Shuhua Lv; Hongyu Mou; Qingjia Liu; Dongrun Li; Lei Feng; Debao Wang; et al. (Chemical Engineering Journal, 2025)

Developing the chemistry module for 27 fluorinated greenhouse gases (F-gases): Reactions, emissions, and implementation in GEOS-Chem - Yali Li; Lei Zhu; Juan Li; Yuyang Chen; Luke M. Western; Dickon Young; Jens Mühle; Ray F. Weiss; Paul B. Krummel; Chris R. Lunder; Song Liu; Xicheng Li; et al. (Atmospheric Environment, 2025)

Comparative Physiological and Proteomic Analyses of Taxillus chinensis Seeds Under Chilling Stress - Limei Pan; Qianping Chen; Lisha Song; Lingyun Wan; Juan Huo; Linxuan Li; Shugen Wei (Plant Molecular Biology Reporter, 2025)

Different Intensities of Exercise Affect the Prognosis of Ventricular Aneurysm in Mice by Regulating the Progression of Cardiac Fibrosis - Rui-Qiang Qi; Juan Song; Hong-Bin Ma; Mei-Ling Nie; Liu-Hang Su; Cui-Lian Dai; Fa-Guang Zhou; Sui-Ji Li (Cardiovascular Toxicology, 2025)

Elucidating the material basis and therapeutic mechanisms of Shaoma Zhijing granules for tourette syndrome by UPLC/Q-TOF-MS and multiple models - Qian Zhao; Xin-Xin Xu; Jin-Na Yang; Li-Juan Pei; Zhou-Yi Xie; Wen-Jia Wang; Jing-Xuan Fu; Zhao-Hui Song; He Sun; Kai-Jing Yan; Hui Wang; Yun-Hui Hu (Metabolic Brain Disease, 2025)

Limonoids and protolimonoid from Swietenia macrophylla - Yun-Peng Sun; Wen-Fang Jin; Ze-Rong Xu; Ying-Wei Liu; Li-Juan Sun; Yang Yu; Jin-Song Liu; Guo-Kai Wang (Natural Product Research, 2025)

Unraveling Qu-aroma variation between inner and outer layers of medium-temperature Daqu: A multi-omics and sensory approach - Sheng-Bing Yang; Zhen-Ming Lu; Han-Jun Shen; Jun-Jie Fu; Yang Yang; Xiao-Juan Zhang; Li-Juan Chai; Song-Tao Wang; Su-Yi Zhang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (International Journal of Food Microbiology, 2025)

Comprehensive analysis of microbial communities, metabolites, and biogenic amines in bagged fermented chili paste at varying salt levels - Wei-Qin Deng; Zhen-Ming Lu; Ze-Liang Wang; Si-Qiang Jiang; Xiong-Bo Li; Zhi-Yi Fan; Xiao-Juan Zhang; Li-Juan Chai; Qi-Sheng Zhang; Jin-Song Shi; Gong Chen; Zheng-Hong Xu (Food Bioscience, 2025)

Targeted metabolomics reveals tricarboxylic acid cycle-related metabolites serve as predictive biomarkers for trastuzumab resistance in human epidermal growth factor receptor 2-positive breast cancer - Ting Yang; Bangbang Wei; Min Wang; Yu Wang; Yiwei Cao; Debang Li; Hongyan Song; Juan Wei; Xinxin Si (Journal of Molecular Medicine, 2025)

High efficacy of (Z)-ligustilide in inhibiting postharvest apple ring rot and its antifungal mechanism against Botryosphaeria dothidea - Xiao-Yi Tong; Li-Li Song; Hui-Fang Du; Ya-Hui Zhang; Jia-Wen Shou; Cai-Juan Zheng; Wen-Bin Gao; Zhong-Cheng Liu; Du-Qiang Luo; Yun-Feng Liu; Fei Cao (Postharvest Biology and Technology, 2025)

Evolution of global O3-NOx-VOCs sensitivity before and after the COVID-19 from the ratio of formaldehyde to NO2 from satellite observations - Dakang Wang; Dongchuan Pu; Isabelle De Smedt; Lei Zhu; Xiankun Yang; Wenfu Sun; Hui Xia; Zhaolong Song; Xicheng Li; Juan Li; Aoxing Zhang; Xu Feng; et al. (Journal of Environmental Sciences, 2025)

Adaptive responses and molecular mechanisms of Lactiplantibacillus plantarum to citric acid stress - Han Xie; Wei Zhang; Cong-Rong Shi; Rui-Shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (International Journal of Food Microbiology, 2025)

Applications and prospects of tin-based electrode materials in lithium/sodium ion capacitors - Juan An; Mingyuan Pang; Qianqian Yang; Haohao Zhang; Jiajia Ye; Zhen Kong; Min Yang; Dan Xu; Yen Leng Pak; Wei Liu; Jibin Song; Guoxing Li (Desalination, 2025)

Targeted gene therapy for intracranial aneurysm using SOX17-CRISPRa - Dujie Xie; Yi Yuan; Panyao Long; Juan Huang; Mi Jiang; Yongzhong Tang; Yuanqiang Luo; Cancan Zhang; Ping Zheng; Liang Yang; Yiwei Chen; Xiaobo Li; et al. (Chemical Engineering Journal, 2025)

Oxidase-mimic Fe-co-Ce oxide embellished chitosan fiber for quantitative degradation of luminol and visual detection of m-aminophenol - Lei Hu; Junkai Hao; Ruhui Shang; Huitian Zhi; Xujie Wang; Yingchao Yang; Hanning Song; Chenxi Li; Juan Yu; Zhengquan Yan (Analytica Chimica Acta, 2025)

Diterpene-phenylpropanoid hybrids and structurally diverse diterpenoid monomers from the endangered conifer Podocarpus annamiensis and their bioactivities - Chi Song; Ze-Yu Zhao; Yi Zang; Jia Li; Yeun-Mun Choo; Haibo Wang; Guangyao Mei; Juan Xiong; Jin-Feng Hu (Phytochemistry, 2025)

Long-term cadmium stress influenced the immune response of Pardosa pseudoannulata by modulating its gut microbiota and hemolymph metabolome - Jinjin Li; Yuan-de Peng; Rong Zhou; Jie Peng; Qingling She; Xinyi Yang; Juan Wang; Zhi Wang; Qisheng Song (Journal of Environmental Sciences, 2025)

Investigation on quality discrepancies of Soy Sauce Aroma Baijiu: Flavor chemical characteristics in single-source and cross-source samples - Chen Li; Xiao-Juan Zhang; Shi-Yi Wang; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Song-Tao Wang; Bo Yang; Cai-Hong Shen; Zheng-Hong Xu (Food Control, 2025)

Wheat stripe rust resistance gene Yr9, derived from rye, is a CC-NBS-LRR gene in a highly conserved NLR cluster - Yang Yu; Jiajun Liu; Shengjie Lan; Qihang Chen; Jinlong Li; Haoyuan Song; Chen Pan; Juan Qi; Yu Cui; Xingfeng Li; Ming-Cheng Luo; Fei Ni; et al. (Science China Life Sciences, 2025)

Plant morphological and physiological traits are stable in a nitrogen-saturated tropical forest after 18-year nitrogen additions - Guangcan Yu; Jing Chen; Andi Li; Senhao Wang; Liang Song; Xianmeng Shi; Junhua Yan; Meichen Xu; Yuewei Xue; Xiankai Lu; Wei Zhang; Juan Huang; et al. (Plant and Soil, 2025)

Effects of Continuous Grafting on the Growth and Selenium Accumulation Characteristics in the Post-Generations of Tomato - Shiling Meng; Xiaoli Song; Wende Zhou; Juan Huang; Yatian Zhao; Wanjia Tang; Yi Tang; Bo Sun; Huanxiu Li; Zhi Huang (Journal of Soil Science and Plant Nutrition, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Efficiently hydrogenolysis of aromatic ether C-O bonds in lignite and model compounds over carbon-coated NiCo bimetallic catalyst - Caitao Chen; Juan Ma; Yakun Tang; Xiaohui Li; Guangbo Liu; Hanyao Song; Yingluo He; Noritatsu Tsubaki; Lang Liu; Ting Liu (Fuel, 2025)

Electrochemiluminescence platform for curcumin detection based on g-C3N4 of N-rich vacancy and Ti2AlC - Yujia Song; Li Tian; Ruidan Li; Yanjia Guo; Pengfei Han; Guangping Ma; Hanyue Jiang; Wenzhuo Wang; Juan Lu (Food Chemistry, 2025)

Dual-potential ratiometric electrochemiluminescence platform based on PCN and Ti3CN@luminol for kanamycin detection in milk samples - Chao Li; Juan Lu; Yanjia Guo; Yujia Song; Ruidan Li; Hanyue Jiang; Wenzhuo Wang; Pengfei Han; Guangping Ma; Jing Wang; Li Tian (Food Chemistry, 2025)

Mixed-linker Zr-based metal-organic framework as a highly sensitive probe for ultrafast and selective detection of fluoride ions - Juan Chen; Tingting Guo; Hongyi Gao; Han Meng; Zhixin Zhang; Jie Li; Zhili Song; Xingyu Pei; Supakorn Boonyuen; Xiaowei Zhang; Yu Jiang; Jinzhang Tao (Environmental Research, 2025)

Comparative analysis of the effects of different dimensionality reduction algorithms on hyperspectral estimation of total nitrogen content in wheat soils - Juan Bai; Shiyou Zhu; Yingchao Hao; Xinzhe Li; Chenbo Yang; Chao Wang; Xingxing Qiao; Meichen Feng; Lujie Xiao; Xiaoyan Song; Meijun Zhang; Sha Yang; et al. (European Journal of Agronomy, 2025)

Water limitation as a driver of species richness decline in global grasslands under nutrient addition - Hailing Li; Josep Peñuelas; Scott L. Collins; Jordi Sardans; Kailiang Yu; Chao Song; Juan Chen; Jian-Sheng Ye (Plant and Soil, 2025)

Semaphorin 3A protects against thoracic aortic aneurysm dissection by suppressing aortic angiogenesis - Li-Fei Wu; Jiao-Jiao Zhang; Xing Zhang; De-Ping Wang; Zhi-Fa Zheng; Jing Shen; Ying Zhou; Li-Juan Gao; Xuan Shang; Jun-Ya Ning; Qing-Hua Liu; Lan Zhou; et al. (Angiogenesis, 2025)

Time series comparative genomics analysis reveals the adaptive evolution of caproic acid-producing bacteria to the long-term liquor brewing environment - Gan-Lin Li; Jun-Lan Mei; Li-Juan Chai; Xiao-Zhong Zhong; Ya-Ning Song; Zhen-Ming Lu; Xiao-Juan Zhang; Song-Tao Wang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (Food Bioscience, 2025)

Mesenchymal stem cell exosomes regulate TGFβ/Smad3 by decreasing the METTL3-NEAT1 axis to inhibit scar progression after breast surgery - Juan Du; Jincheng Wu; Qinqin Song; Shuangru Li; Youwang Hong; Aizaz Anwar; Quanyou Fu; Jisong Liu (Journal of Molecular Histology, 2025)

Per- and polyfluoroalkyl substances (PFAS) in drinking water systems in the lower Yangtze River: source, fate, and health risk assessment - Yuan Hong; Qin Ding; Tingting Yang; Xiaoqin Li; Ninghui Song; Juan Zhang (Environmental Geochemistry and Health, 2025)

Record High Temperatures in the Ocean in 2024 - Lijing Cheng; John Abraham; Kevin E. Trenberth; James Reagan; Huai-Min Zhang; Andrea Storto; Karina Von Schuckmann; Yuying Pan; Yujing Zhu; Michael E. Mann; Jiang Zhu; Fan Wang; et al. (Advances in Atmospheric Sciences, 2025)
Heating in the ocean has continued in 2024 in response to increased greenhouse gas concentrations in the atmosphere, despite the transition from an El Niño to neutral conditions. In 2024, both global sea surface temperature (SST) and upper 2000 m ocean heat content (OHC) reached unprecedented highs in the historical record. The 0–2000 m OHC in 2024 exceeded that of 2023 by 16 ± 8 ZJ (1 Zetta Joules = 10 21 Joules, with a 95% confidence interval) (IAP/CAS data), which is confirmed by two other data products: 18 ± 7 ZJ (CIGAR-RT reanalysis data) and 40 ± 31 ZJ (Copernicus Marine data, updated to November 2024). The Indian Ocean, tropical Atlantic, Mediterranean Sea, North Atlantic, North Pacific, and Southern Ocean also experienced record-high OHC values in 2024. The global SST continued its record-high values from 2023 into the first half of 2024, and declined slightly in the second half of 2024, resulting in an annual mean of 0.61°C ± 0.02°C (IAP/CAS data) above the 1981–2010 baseline, slightly higher than the 2023 annual-mean value (by 0.07°C ± 0.02°C for IAP/CAS, 0.05°C ± 0.02°C for NOAA/NCEI, and 0.06°C ± 0.11°C for Copernicus Marine). The record-high values of 2024 SST and OHC continue to indicate unabated trends of global heating.

Contamination, multimedia partitioning, and priority list of steroids and their metabolites in coastal regions of the Greater Bay Area, China - Qin-Ge Zhou; Shan Liu; Yuan Liu; Nian-Nian Wu; Qing-Song Yang; Heng-Xiang Li; Xiang-Rong Xu; Juan Ling (Process Safety and Environmental Protection, 2025)

Enhancing fruit quality through unraveling the molecular and physiological basis and preventing cracking in jujube (Ziziphus jujuba Mill.) - Hong-Xiang Zhou; Run-Zhe Wang; Wen-Ting Luo; Yang Liang; Shi-Yu Liu; Juan Chen; Ji-Qing Peng; Yan-Xia Fan; Shu-Zhan Li; Chuan Guo; Zi-Qiang Zhang; Feng-Xia Shao; et al. (Postharvest Biology and Technology, 2025)

Tracing the Changjiang-derived sediments along the southeast coast of China during the Holocene - Yalong Li; Xin Shan; Xiangtong Huang; Zhanghua Wang; Jianhua Gao; Ping Yin; Quanhong Zhao; Juan Xu; Zhen Song; Shouye Yang (Global and Planetary Change, 2025)

Nitrogen and phosphorus in water-sediment system of eutrophic lake amended with biochar-supported Effective Microorganisms: Temporal variation and remediation - Siqun Tang; Jilai Gong; Juan Li; Biao Song; Weicheng Cao; Jun Zhao (Journal of Environmental Management, 2025)

Lactic acid bacteria-mediated transformation of black tea extract: Insights into metabolite profile and sensory characteristics - Zhi-Peng Cheng; Yao-Zeng Zhang; Zhong-Zheng Guan; Rui-shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (Food Bioscience, 2025)

A Revisit of Landsat-Observed Macroalgal Blooms in the Yellow Sea and East China Sea Before 2008 - Chao Yuan; Juan Huang; Lingjuan Wu; Jie Xiao; Xuelei Zhang; Song Gao; Yifei Li; Jiangling Xu; Zongling Wang (Journal of Ocean University of China, 2025)

Comparative Analysis of Amino Acid Composition, Fatty Acid Profiles, and Genetic Diversity Among Three Populations of Penaeus semisulcatus - Yundong Li; Juan Chen; Ziyi Jiang; Song Jiang; Qibin Yang; Lishi Yang; Jianhua Huang; Jianzhi Shi; Yangyang Ding; Tianmi Liu; Falin Zhou (Journal of Marine Science and Engineering, 2025)
Penaeus semisulcatus, a commercially valuable aquaculture species, is widely distributed along the southeastern coast of China and throughout the South China Sea. Despite its economic importance, the comprehensive understanding of its germplasm characteristics remains limited. This investigation evaluated nutrient profiles, amino acid composition, lipid constituents, antioxidant capacity, and genomic variability across three farmed aquaculture populations maintained under standardized environmental parameters to discern divergence in nutritive attributes and hereditary characteristics. The results revealed significant interpopulation variation in ash content (p

Untargeted qualitative and targeted quantitative analysis of saponins reveal differential chemotypes of Gynostemma pentaphyllum and G. longipes from different geographical origins - Hai-Zhen Liang; Mei-Yan Wang; Guang Yang; Gang Li; Jie Zhang; Lan Yao; Yi Nan; Chang-Liang Huang; Xiao-Juan Chen; Juan Song; Feng Cao; Bao-Lin Guo; et al. (Food Chemistry, 2025)

Yeast community in the first-round fermentation of sauce-flavor Baijiu: Source, succession and metabolic function - Zheng-Pei Chen; Qian Cao; Tian-Tian Meng; Wei Shi; Xiao-Juan Zhang; Li-Juan Chai; Jin-Song Shi; Fu-Wei Chen; Song-Tao Wang; Su-Yi Zhang; Cai-Hong Shen; Zhen-Ming Lu; et al. (Food Research International, 2025)

Overexpression of OsSTP1 increases grain yield via enhancing carbohydrate metabolism and transport in rice - Dong Liu; Ming-juan Li; Jin-song Luo; Hai-fei Chen; Yong Yang; Gui Xiao; Jun Wu; Abdelbagi M. Ismail; Zhen-hua Zhang (Planta, 2025)

Remediation of biochar-supported effective microorganisms and microplastics on multiple forms of nitrogenous and phosphorous in eutrophic lake - Siqun Tang; Jilai Gong; Biao Song; Juan Li; Weicheng Cao; Jun Zhao (Science of The Total Environment, 2024)

Modification of gut and airway microbiota on ozone-induced airway inflammation - Fei Xu; Qiong Wu; Lin Yang; Han Sun; Juan Li; Zhen An; Huijun Li; Hui Wu; Jie Song; Wen Chen; Weidong Wu (Science of The Total Environment, 2024)

Biodegradation of imidacloprid and diuron by Simplicillium sp. QHSH-33 - Ke Xu; Xin-Ran Ke; Wan-Ting Zhang; Xin-Yuan Wu; Zhi-Jun Song; Mei-Juan Jiao; Xiao-Juan Gao; Li Zhou; Hong-Yan Ji; Fang Wang; Xiu-Li Wu (Pesticide Biochemistry and Physiology, 2024)

Concurrent ozone and high temperature exacerbates nasal epithelial barrier damage in allergic rhinitis mice: Insights from the nasal transcriptome and nasal microbiota - Juan Li; Huai Wei; Ning Wang; Jing Chen; Weiping Zhang; Zhen An; Jie Song; Yixuan Liang; Xiaowan Liu; Weidong Wu (Journal of Hazardous Materials, 2024)

Seasonality shapes the microbiota and metabolome of strong-flavor Baijiu during fermentation and affects its flavor characteristics - Li-Juan Chai; Jing-Yi Zhang; Tao Gao; Long-Yun Zhang; Xiao-Juan Zhang; Zhen-Ming Lu; Jin-Song Shi; Xiang Chen; Zheng-Hong Xu (Food Bioscience, 2024)

Mitochondrial dysfunction induced by ambient fine particulate matter and potential mechanisms - Zhen An; Guangyong Liu; Lingling Shen; Yongmei Qi; Qinan Hu; Jie Song; Juan Li; Jinge Du; Yichun Bai; Weidong Wu (Environmental Research, 2024)

Effects of Hydraulic Residence Time, NO3− and NO2− on Sulfate-Reducing Anaerobic Ammonium Oxidation Reaction - Siyu Shao; Li Cui; Danqi Wang; Juan Lu; Fan Qiu; Jia Bao; Xiaoxiong Song (Water, Air, & Soil Pollution, 2024)

Community of Arbuscular Mycorrhizal Fungi in the Rhizosphere Soils with Different Generations of Hybridized Progeny of Wild Erianthus arundinaceus and Sugarcane - Jin-Lian Zhang; Yi-Hao Kang; Juan Song; Huan-Ying Xu; Wei Zhang; Ying-Jie Nong; Qian Wang; Qin-Nan Wang; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2024)

Effects of Mutual Grafting on Fruit Quality in Post-grafting generation of Two Genotypes Cherry Tomato (Lycopersicon esculentum) - Zhi Huang; Shiling Meng; Huizhong Luo; Wende Zhou; Juan Huang; Yatian Zhao; Xiaoli Song; Yi Tang; Bo Sun; Huanxiu Li (Journal of Soil Science and Plant Nutrition, 2024)

Simultaneous determination of somatic cell count and total plate count in raw milk based on ATP bioluminescence assay - Longrui Yang; Xiaoyun Sun; Jiaci Chen; Juan Zhang; Xiaoyu Li; Song Qu; Kai Wu; Fengchun Huang; Ailiang Chen (Analytica Chimica Acta, 2024)

A comprehensive study on nutritional quality, physiological enzyme activity and genetic diversity in six populations of Penaeus monodon - Yundong Li; Juan Chen; Shigui Jiang; Jianhua Huang; Song Jiang; Qibin Yang; Lishi Yang; Jianzhi Shi; Falin Zhou (Aquaculture International, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Global genomic epidemiology and transmission dynamics of plasmid-borne tmexCD-toprJ-carrying Klebsiella pneumoniae in a one health context - Hao Guo; Lirong Li; Yingying Zhang; Yawen Zhang; Che Song; Yuye Wu; Juan Xu; Zhi Ruan; Fang He (Science of The Total Environment, 2024)

Innovative active disturbance motion control for an underwater adsorption wall-climbing robot with uncertainties and compensations - Tingting Guo; Xu Zhang; Juan Li; Dalei Song; Xiuyan Liu (Ocean Engineering, 2024)

Peering through the hedge: Multiple datasets yield insights into the phylogenetic relationships and incongruences in the tribe Lilieae (Liliaceae) - Deng-Feng Xie; Juan Li; Jia-Hui Sun; Rui-Yu Cheng; Yuan Wang; Bo-Ni Song; Xing-Jin He; Song-Dong Zhou (Molecular Phylogenetics and Evolution, 2024)

Pyridoxal phosphate promotes the γ-aminobutyric acid accumulation, antioxidant and anti-hypertensive activity of germinated tartary buckwheat - Huiling Yan; Hongxu Chen; Juan Liu; Tian Yao; Mengying Xia; Qingxia Liao; Ludong Huang; Wanjie Li; Yu Song; Lianxin Peng; Jianglin Zhao; Liang Zou; et al. (Journal of Cereal Science, 2024)

Decoding the Qu-aroma of medium-temperature Daqu starter by volatilomics, aroma recombination, omission studies and sensory analysis - Sheng-Bing Yang; Jun-Jie Fu; Jia-Huan He; Xiao-Juan Zhang; Li-Juan Chai; Jin-Song Shi; Song-Tao Wang; Su-Yi Zhang; Cai-Hong Shen; Zhen-Ming Lu; Zheng-Hong Xu (Food Chemistry, 2024)

Acacetin targets STING to alleviate the destabilization of the medial meniscus-induced osteoarthritis in mice - Dingjun Xu; Linjie Zhang; Chenyu Song; Dinglei Zhang; Chunlei Xing; Juan Lv; Huihui Bian; Minyu Zhu; Minxuan Han; Yongsheng Yu; Li Su (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Ozone-Induced Lung Injury are Mediated Via PPAR-Mediated Ferroptosis in Mice - Juan Li; Huai Wei; Ning Wang; Jing Chen; Ying Zhang; Zhen An; Jie Song; Tianqi Niu; Weidong Wu (Biological Trace Element Research, 2024)

EtROP38 suppresses apoptosis of host cells infected with Eimeria tenella by inhibition of the p38MAPK pathway - Bu-ting Duan; Hao-yu Zhang; Zi-hao Song; Xiao-yi Han; Kai-ling Cui; Tong Xu; Yu Zhang; Yong-juan Zhao; Xuan Lei; Fan Tan; Lu-lu Guo; Hui-lin Yang; et al. (Veterinary Parasitology, 2024)

The protective effect of glucose selenol on cadmium-induced testicular toxicity in male rat - Xinyi Yang; Jinzhou Huang; Juan Wang; Huimin Sun; JinJin Li; Zhi Wang; Qisheng Song (Reproductive Toxicology, 2024)

Study on the grading preparation of multifunctional materials and application from coal gasification fine slag - Song Qiao; Yulong Ma; Yonggang Sun; Li Zhu; Jing Ma; Jingdan Gao; Yingbo Zhu; Juan Zhang; Lei Wang; Min Xu; Yuhua Wu; Wenxin Ji; et al. (Process Safety and Environmental Protection, 2024)

Multigenerational effects of disperse blue 79 at environmentally relevant concentrations on zebrafish (Danio rerio) fecundity: An integrated approach - Chao Wang; Wen Gu; Shaoping Zhang; Li Li; Jian Kong; Hong Zhi; Juan Liu; Mengmeng Wang; Ke Miao; Qi Li; Jie Yu; Runming Wang; et al. (Journal of Hazardous Materials, 2024)

Environmental water-mediated dual-mechanism regulation of PtCuδ-MnOx-catalyzed acetone oxidation: Enhancement of MvK and inhibition of L-H mechanism - Lei Wang; Xin Zhang; Yonggang Sun; Yulong Ma; Min Xu; Juan Zhang; Yingbo Zhu; Li Zhu; Song Qiao; Jing Ma; Jinpeng Wei; Feng Lin (Journal of Environmental Chemical Engineering, 2024)

Optimization of differentiation conditions for porcine adipose-derived mesenchymal stem cells and analysis of fatty acids in cultured fat - Pei-Pei Liu; Zi-Jiang Yang; Wen-Juan Song; Shi-Jie Ding; Hui-Xia Li; Chun-Bao Li (Food Research International, 2024)

Deciphering the effects of different types of high-temperature Daqu on the fermentation process and flavor profiles of sauce-flavor Baijiu - Wei Shi; Li-Juan Chai; Han Zhao; Ya-Ning Song; Jun-Lan Mei; Yang-Xue He; Zhen-Ming Lu; Xiao-Juan Zhang; Bo Yang; Song-Tao Wang; Cai-Hong Shen; Zheng-Hong Xu (Food Bioscience, 2024)

Comparative genomics of Clostridium tyrobutyricum reveals signatures of environment-specific adaptation and metabolic potentials - Guan-Yu Fang; Li-Juan Chai; Zhen-Ming Lu; Xiao-Juan Zhang; Hong-Yu Xu; Song-Tao Wang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (Food Bioscience, 2024)

LncRNA 51A: A promising diagnostic biomarker for assessing cognitive decline in occupationally exposed aluminum workers - Hailun Fang; Juan Li; Lei Zhang; Baichun Li; Jing Song; Xiaoting Lu; Qiao Niu; Linping Wang (Environmental Toxicology and Pharmacology, 2024)

Intelligent operation-activated dual light-up nanointerrogator for on-site high-performance bioimaging - Tiantian Li; Yingying Li; Die Hu; Yu Luo; Weiling Song; Peng He; Jing-Juan Xu; Hong Zhou (Chemical Engineering Journal, 2024)

Bayesian inversion of HFC-134a emissions in southern China from a new AGAGE site: Results from an observing system simulation experiment - Juan Li; Jianxiong Sheng; Lei Zhu; Bo Yao; Jing Wu; Dongchuan Pu; Lei Shu; Song Liu; Xicheng Li; Yuyang Chen; Xiaoxing Zuo; Yali Li; et al. (Atmospheric Environment, 2024)

Promoting sustainable development by mitigation of natural habitat quality decline through multifunctional urban land use: Insights from a multi-scenario simulation - Houxing Gao; Xiaoqing Song; Huixiao Xu; Xiang Li; Juan Tang; Guosong Zhao (Sustainable Cities and Society, 2024)

Bioreduction of Se(IV) by Lactiplantibacillus plantarum NML21 and synthesis of selenium nanospheres Se(0) - Longlin Wang; Li Song; Pengjie Wang; Hao Zhang; Yiheng Li; Juan Song; Liwen Zhong; Caihong Liu; Weibing Zhang; Pengcheng Wen (Food Chemistry, 2024)

Norwogonin aids in fighting MRSA-induced pneumonia by targeting agrAC to inhibit α-hemolysin production - Chang Liu; Juan Hou; Xinran Ren; Xuerui Guo; Bingmei Wang; Wu Song; Li Wang; Guangshu Wang (World Journal of Microbiology and Biotechnology, 2024)

Current insights into environmental acetochlor toxicity and remediation strategies - Wen-Juan Chen; Shao-Fang Chen; Haoran Song; Zeren Li; Xiaofang Luo; Xidong Zhang; Xiaofan Zhou (Environmental Geochemistry and Health, 2024)

Metagenomic Profiling of Bacterial Communities and Functional Genes in Penaeus monodon - Juan Chen; Yundong Li; Song Jiang; Qibin Yang; Jianhua Huang; Lishi Yang; Jianzhi Shi; Zhibin Lu; Yan Zhang; Shigui Jiang; Falin Zhou (Journal of Marine Science and Engineering, 2024)
Penaeus monodon is one of the world’s most important aquaculture species, with its host-associated microbial community playing a crucial role in its growth, metabolism, immune response, and adaptation. In our study, we utilized Illumina high-throughput sequencing to investigate the composition, structure, and function of the intestinal microbial communities of P. monodon from two different regions in Guangdong. Our results identified 176 phyla across both populations, with Proteobacteria and Firmicutes being predominant. Furthermore, we identified 3095 genera, with Photobacterium, Vibrio, and Aliiroseovarius being the most dominant. Functional gene analysis based on KEGG data indicated that the carbohydrate metabolism and amino acid metabolism were significant at the secondary metabolic pathway level. The eggNOG functional annotation revealed that the genes involved in replication, recombination, and repair are of paramount importance. The CAZy annotation results indicated that Glycoside Hydrolases (GH) have the highest abundance. The Pfam annotation analysis showed that the two most prevalent domains are P-loop NTPase and NADP Rossmann. Our investigation provides a reference for species-level and functional-level analyses of the intestinal microbiota of P. monodon, contributing valuable insights into its microbial ecology.

A novel bio-based film-forming helper derived from Leuconostoc mesenteroides: A promising alternative to chemicals for the preparation of biomass film - Yukun Chen; Xiaofang Gong; Jie Song; Yinan Peng; Yang Zeng; Juan Chen; Zhiye Wang; Zhilong Li; Ying Zhu (Chemical Engineering Journal, 2024)

Alleviating Pentatrichomonas hominis-induced damage in IPEC-J2 cells: the beneficial influence of porcine-derived lactobacilli - Yibin Zhu; Haiming Cai; Zhuanqiang Yan; Hanqin Shen; Siyun Fang; Dingai Wang; Shenquan Liao; Nanshan Qi; Minna Lv; Xuhui Lin; Junjing Hu; Yongle Song; et al. (Veterinary Research Communications, 2024)

Glutathione-activated biotin-targeted dual-modal imaging probe with improved PDT/PTT synergistic therapy - Zhi-Chao Yang; Qing-Song Gu; Jing-Jing Chao; Fang-Yuan Tan; Guo-Jiang Mao; Liufang Hu; Juan Ouyang; Chun-Yan Li (Analytica Chimica Acta, 2024)

Effects of Angle of Attack on Flow-Induced Vibration of a D-Section Prism - Shiguang Fan; Zhuang Li; Jining Song; Xietian Du; Juan Wang (Journal of Marine Science and Engineering, 2024)
The VIVACE device, which utilizes flow-induced vibration for harvesting ocean current energy, has been a research hotspot in the field of renewable energy. In this study, the flow-induced vibration characteristics and energy conversion efficiency of a D-section prism were investigated using the k-ω SST turbulence model and Newmark-β method. The vibration amplitude, frequency, equilibrium position offset, and energy conversion efficiency of the two-degree-of-freedom cylinder were systematically analyzed at seven angles of attack between 0 and 180 degrees. The Reynolds number ranged from 368 to 14,742, corresponding to equivalent speeds of 2 to 20. The results indicate that the angle of attack has a significant influence on the flow-induced vibration response of the D-section prism. As the angle of attack changes, the vibration amplitude of the cylinder continuously increases, and the cylinder sequentially enters the vortex-induced vibration, vortex-induced vibration-galloping, and fully galloping branches. The change in the angle of attack disrupts the symmetry of the cylinder’s vibration in the streamwise direction, leading to a shift in the equilibrium position of the cylinder’s vibration. When the angle of attack is 0°, the energy conversion efficiency of the column reaches a maximum of 11.75%. Additionally, at high Reynolds numbers, the vibration of the cylinder is not self-limiting, making it more advantageous for energy conversion devices compared to cylinders with circular cross-sections.

Optimized design of quaternary amino-functionalized chitosan fibers for ultra-high diclofenac adsorption from wastewater - Xiaoyu Lin; Myung-Hee Song; Wenhao Li; Wei Wei; Xiaohui Wu; Juan Mao; Yeoung-Sang Yun (Chemosphere, 2024)

Annamiacids A and B: Two dissymmetric bis-diterpenes containing a rare ketal-γ-lactone motif from Podocarpus annamiensis and their inhibitory effects on ATP-citrate lyase - Chi Song; Ze-Yu Zhao; Jin-Xin Zhu; Yi Zang; Juan Xiong; Jia Li; Jin-Feng Hu (Phytochemistry Letters, 2024)

Pseudo-targeted lipidomics insights into lipid discrepancies between yak colostrum and mature milk based on UHPLC-Qtrap-MS - Yiheng Li; Huiyuan Guo; Xue Yang; Xiaoli Yang; Hao Zhang; Pengjie Wang; Juan Song; Longlin Wang; Weibing Zhang; Pengcheng Wen (Food Chemistry, 2024)

Co4+ in porous ZIF-67-derives intercalating-bridging adsorption of 2-reaction sites for simultaneous 2-electron transfer toward sensitive detection of uric acid - Li Peng Gan; Juan Li; Fan Shi; Zhuo Zou; Ke Jiang Li; Zhuan Zhuan Shi; Xiao Shuai Wu; Yun Peng Li; Wei Sun; Zhi Song Lu; Tao Hu; Liming Dai; et al. (Analytica Chimica Acta, 2024)

Co-influence of biochar-supported effective microorganisms and seasonal changes on dissolved organic matter and microbial activity in eutrophic lake - Siqun Tang; Jilai Gong; Biao Song; Juan Li; Weicheng Cao; Jun Zhao (Science of The Total Environment, 2024)

Exploring the release mechanism of micro/nanoplastics from different layers of masks in water: towards reduction of plastic contamination in masks - Wei Ge; Hao Liang; Ping Gao; Yan Li; Ningning Song; Juan Wu; Chao Chai (Environmental Science and Pollution Research, 2024)

The emerging role of zinc on alleviating inflammatory responses and enhancing immunity in grass carp (Ctenopharyngodon idella) - Xin Zeng; Zheng-Xing Song; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; Ling Tang; Shu-Wei Li; Juan Yang; Lin Feng (Aquaculture, 2024)

Immunoprotective effects of DNA vaccine against Eimeria tenella based on EtAMA3 and EtRON2L2 - Xiangjie Chen; Xixi Qiu; Junli Ni; Shenquan Liao; Nanshan Qi; Juan Li; Minna Lv; Xuhui Lin; Haiming Cai; Junjing Hu; Yongle Song; Lijun Yin; et al. (Veterinary Parasitology, 2024)

Nitrogen isotopic characteristics of aerosol ammonium in a Chinese megacity indicate the reduction from vehicle emissions during the lockdown period - Zhengjie Li; Hongwei Xiao; Wendell W. Walters; Meredith G. Hastings; Juan Min; Linlin Song; Weizhi Lu; Libin Wu; Wende Yan; Shuguang Liu; Yunting Fang (Science of The Total Environment, 2024)

Effects of lianas on forest biogeochemistry during their lives and afterlives - Gbadamassi G. O. Dossa; Hong‐Lin Li; Bo Pan; Tial C. Ling; Douglas A. Schaefer; Mareike Roeder; Denis M. Njoroge; Juan Zuo; Liang Song; Bismark Ofosu‐Bamfo; Stefan A. Schnitzer; Rhett D. Harrison; et al. (Global Change Biology, 2024)
Climate change and other anthropogenic disturbances are increasing liana abundance and biomass in many tropical and subtropical forests. While the effects of living lianas on species diversity, ecosystem carbon, and nutrient dynamics are receiving increasing attention, the role of dead lianas in forest ecosystems has been little studied and is poorly understood. Trees and lianas coexist as the major woody components of forests worldwide, but they have very different ecological strategies, with lianas relying on trees for mechanical support. Consequently, trees and lianas have evolved highly divergent stem, leaf, and root traits. Here we show that this trait divergence is likely to persist after death, into the afterlives of these organs, leading to divergent effects on forest biogeochemistry. We introduce a conceptual framework combining horizontal, vertical, and time dimensions for the effects of liana proliferation and liana tissue decomposition on ecosystem carbon and nutrient cycling. We propose a series of empirical studies comparing traits between lianas and trees to answer questions concerning the influence of trait afterlives on the decomposability of liana and tree organs. Such studies will increase our understanding of the contribution of lianas to terrestrial biogeochemical cycling, and help predict the effects of their increasing abundance.

Remediation of biochar-supported effective microorganisms and microplastics on multiple forms of heavy metals in eutrophic lake - Siqun Tang; Jilai Gong; Biao Song; Weicheng Cao; Juan Li (Journal of Hazardous Materials, 2024)

Influence on the volatilization of ethyl esters: Nonnegligible role of long-chain fatty acids on Baijiu flavor via intermolecular interaction - Qing-Ru Liu; Xian-Li Lin; Zhen-Ming Lu; Li-Juan Chai; Song-Tao Wang; Jin-Song Shi; Su-Yi Zhang; Cai-Hong Shen; Xiao-Juan Zhang; Zheng-Hong Xu (Food Chemistry, 2024)

Association of short-term PM2.5 exposure with airway innate immune response, microbiota and metabolism alterations in human airways - Shuaiqi Zhao; Huijun Li; Fuyun Yang; Yishu Yang; Yuling Zeng; Zhen An; Juan Li; Hui Wu; Jie Song; Weidong Wu (Environmental Pollution, 2024)

Optimal dietary protein level for the growth and metamorphosis of bullfrog (Lithobates catesbeianus) tadpoles - Juan Gao; Xueshan Li; Kangle Lu; Kai Song; Jian Zhang; Ling Wang; Chunxiao Zhang (Aquaculture, 2024)

Community-level bioaugmentation results in enzymatic activity- and aroma-enhanced Daqu through altering microbial community structure and metabolic function - Wen-Hu Liu; Li-Juan Chai; Hong-Mei Wang; Zhen-Ming Lu; Xiao-Juan Zhang; Chen Xiao; Song-Tao Wang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (Food Bioscience, 2024)

Phycoremediation and valorization of hypersaline pickled mustard wastewater via Chaetoceros muelleri and indigenous bacteria - Kai Zhang; Shuqin Jiang; Juan Zhang; Jishu Zheng; Ping Li; Song Wang; Ru Bi; Lihong Gao (Bioresource Technology, 2024)

The Community of Arbuscular Mycorrhizal Fungi in Sugarcane Rhizosphere Soils in Guangxi, China - Jin-Lian Zhang; Juan Song; Yi-Hao Kang; Yun-Ying Wen; Ying-Jie Nong; Qian Wang; Xiao-Juan Qin; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2024)

Icariin ameliorates the cuprizone-induced demyelination associated with antioxidation and anti-inflammation - Li-Juan Song; Qing-Xian Han; Zhi-Bin Ding; Kexin Liu; Xiao-Xu Zhang; Min-Fang Guo; Dong Ma; Qing Wang; Bao-Guo Xiao; Cun-Gen Ma (Inflammopharmacology, 2024)

Experimental and numerical investigation of the expansion mechanism of beam-end expansion devices in large-span bridge - Tao Liao; Juan Song; Jun Lai; Kai Wang; Ping Wang; Zhiheng Li; Jingmang Xu; Yao Qian; Junke Lin (Engineering Structures, 2024)

Tissue-specific populations from amniotic fluid-derived mesenchymal stem cells manifest variant in vitro and in vivo properties - Nengqing Liu; Yi Cheng; Ding Wang; Hongmei Guan; Diyu Chen; Juan Zeng; Dian Lu; Yuanshuai Li; Yinghong Yang; Qian Luo; Lifen Zhu; Bin Jiang; et al. (Human Cell, 2023)
Amniotic fluid derived mesenchymal stem cells (AFMSCs), shed along the fetal development, exhibit superior multipotency and immunomodulatory properties compared to MSCs derived from other somatic tissues (e.g., bone marrow and fat). However, AFMSCs display heterogeneity due to source ambiguity, making them an underutilized stem cells source for translational clinical trials. Consequently, there is an urgent need to identify a method to purify the AFMSCs for clinical use. We found that the AFMSCs can be categorized into three distinct groups: kidney-specific AFMSCs (AFMSCs-K), lung-specific AFMSCs (AFMSCs-L), and AFMSCs with an undefined tissue source (AFMSCs-X). This classification was based on tissue-specific gene expression pattern of single cell colony. Additionally, we observed that AFMSCs-X, a minority population within the AFMSCs, exhibited the highest multipotency, proliferation, resistance to senescence and immuno-modulation. Our results showed that AFMSCs-X significantly improved survival rates and reduced bacterial colony forming units (CFU) in cecal ligation and puncture (CLP)-induced septic mice. Therefore, our study introduces a novel classification method to enhance the consistency and efficacy of AFMSCs. These subpopulations, originating from different tissue source, may offer a valuable and innovative resource of cells for regenerative medicine purposes.

Short-term ozone exposure and serum neural damage biomarkers in healthy elderly adults: Evidence from a panel study - Rongrong Qu; Beibei Sun; Jing Jiang; Zhen An; Juan Li; Hui Wu; Weidong Wu; Jie Song (Science of The Total Environment, 2023)

High temperature exacerbates ozone-induced airway inflammation: Implication of airway microbiota and metabolites - Fei Xu; Qiong Wu; Yishu Yang; Ling Zhang; Zhen Yan; Huijun Li; Juan Li; Zhen An; Hui Wu; Jie Song; Weidong Wu (Science of The Total Environment, 2023)

Limonoids from the roots of Melia azedarach and their anti-inflammatory activity - Min Song; Hui-Juan Luo; Zi-Wei Li; Ling Qiu; Yu-Xin Zhao; Cheng-Wei He; Xiao-Qi Zhang; Wen-Cai Ye; Li-Gen Lin; Qing-Wen Zhang (Phytochemistry, 2023)

Nuclear factor kappa B (NF-κB) participates in the aluminum-induced down-regulation of miR29a/b1 - Linping Wang; Jingqi Zhang; Yue Zhao; Juan Li; Xiaoting Lu; Jing Song; Ling Zhang; Qiao Niu (Journal of Trace Elements in Medicine and Biology, 2023)

Obtention, interaction, and characterization of the soy protein isolate-glycyrrhizin nanocomplex for encapsulating naringenin - Qingchen Cui; Xixi Song; Mengshuang Li; Yanjun Wei; Juan Dong; Xianggen Wu (Food Hydrocolloids, 2023)

A one-pot method based on rolling circle amplification and light‐activated CRISPR/Cas12a reaction for simple and highly sensitive detection of Staphylococcus aureus - Qian Wu; Song Jiang; Yong Huang; Lijun Zhang; Zongying Li; Yongbin Hou; Juan Zhang; Yuwei Wang; Chuanlin Zhu; Dandan Zhou; Weixian Chen; Dandan Li (Chemical Engineering Journal, 2023)

Metabolic engineering combined with enzyme engineering for overproduction of ectoine in Escherichia coli - Lihong Li; Ning Li; Xinglong Wang; Song Gao; Juan Zhang; Jingwen Zhou; Zhimeng Wu; Weizhu Zeng (Bioresource Technology, 2023)

Effects of Mixed Cropping on Sugarcane Growth and the Community of Arbuscular Mycorrhizal Fungi - Ying-Jie Nong; Qian Wang; Juan Song; Jin-Lian Zhang; Xiao-Juan Qin; Yi-Hao Kang; Xiang-Hua Wei; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2023)

Modified Biochar for Arsenic Immobilization in Soil: A Critical Review - Jingzi Beiyuan; Yiyin Qin; Qiqi Huang; Jin Wang; Binoy Sarkar; Nanthi Bolan; Xiaolian Wu; Weicheng Xu; Juan Liu; Xin Chen; Song Xu; Ruyi Hu; et al. (Reviews of Environmental Contamination and Toxicology, 2023)

Photocatalytic degradation of polyethylene and polystyrene microplastics by α-Fe2O3/g-C3N4 - Chao Chai; Hao Liang; Ruike Yao; Fangli Wang; Ningning Song; Juan Wu; Yan Li (Environmental Science and Pollution Research, 2023)

Recent advances in the unlined cast iron pipe scale characteristics, cleaning techniques and harmless disposal methods: An overview - Ming Li; Dong Zhang; Ru Zhang; Fang Wang; Yang Song; Feiyong Chen; Juan Yang; Changming Li (Chemosphere, 2023)

The R2R3-MYB transcription factor CsMYB42 regulates theanine biosynthesis in albino tea leaves - Nianci Xie; Xiangxiang Huang; Jiaxin Zhou; Xiaofeng Song; Junming Lin; Meihong Yan; Mingzhi Zhu; Juan Li; Kunbo Wang (Plant Science, 2023)

New evidence of consistency between phylogeny and morphology for two taxa in ciliated protists, the subclasses Oligotrichia and Choreotrichia (Protista, Ciliophora) - Wen Song; Huixin Jiao; Juan Yang; Danxu Tang; Tingting Ye; Lu Li; Lei Yang; Lifang Li; Weibo Song; Saleh A. Al-Farraj; Hunter N. Hines; Weiwei Liu; et al. (Molecular Phylogenetics and Evolution, 2023)

Geochemical and provenance heterogeneity of small mountainous river systems in Southeast China - Yalong Li; Xiangtong Huang; Ergang Lian; Chao Li; Juan Xu; Ping Yin; Zhen Song; Shouye Yang (Global and Planetary Change, 2023)

Delayed sowing increased dry matter accumulation during stem elongation in winter wheat by improving photosynthetic yield and nitrogen accumulation - Yuangang Zhu; Juan Liu; Jiaqi Li; Lishan Xian; Jinpeng Chu; Hui Liu; Jian Song; Yinghui Sun; Zhongmin Dai (European Journal of Agronomy, 2023)

H2S cracking to produce H2 through microwave discharge catalysis of graphitized petroleum coke - Zhiyang Zhao; Dongqiang Cai; Juan Liu; Guifu Zou; Qiang Zhang; Zhanlong Song; Cuiping Wang; Longzhi Li (Chemical Engineering Journal, 2023)

Multi-valent mRNA vaccines against monkeypox enveloped or mature viron surface antigens demonstrate robust immune response and neutralizing activity - Niubing Zhang; Xiang Cheng; Yilong Zhu; Ouyang Mo; Huiqing Yu; Liqi Zhu; Juan Zhang; Linlin Kuang; Ying Gao; Ruiyuan Cao; Xiaozhen Liang; Haikun Wang; et al. (Science China Life Sciences, 2023)

Tree communities and functional traits determine herbivore compositional turnover - Ming-Qiang Wang; Zhixin Wen; Jinzhao Ke; Douglas Chesters; Yi Li; Jing-Ting Chen; Arong Luo; Xiaoyu Shi; Qing-Song Zhou; Xiao-Juan Liu; Keping Ma; Helge Bruelheide; et al. (Oecologia, 2023)

Genetic diversity and structure of Eurasian otters on Kinmen Island - Nian-Hong Jang-Liaw; Yu-Chun Tan; Chia-Jui Chang; Chung-Hao Juan; Hsuan-Yi Hou; Li-Wai Chung; Huan-Song Cao; Daisuke Waku; Shih-Wei Chang; Ling-Ling Lee (Conservation Genetics, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Dammarane-type saponins from Gynostemma pentaphyllum and their anti-aging activities via up-regulating mitochondria related proteins - Hai-Zhen Liang; Peng-Xin Lu; Li-Li Chu; Gang Li; Chuan-Biao Li; Xiao-Juan Chen; Jie Zhang; Juan Song; Tao Zhang; Ying Luo; Ying Hu; Bai-Ping Ma (Phytochemistry, 2023)

Urbanization shifts long‐term phenology and severity of phytoplankton blooms in an urban lake through different pathways - Yuanrui Li; Juan Tao; Yunlin Zhang; Kun Shi; Junjun Chang; Min Pan; Lirong Song; Erik Jeppesen; Qichao Zhou (Global Change Biology, 2023)
Climate change can induce phytoplankton blooms (PBs) in eutrophic lakes worldwide, and these blooms severely threaten lake ecosystems and human health. However, it is unclear how urbanization and its interaction with climate impact PBs, which has implications for the management of lakes. Here, we used multi‐source remote sensing data and integrated the Virtual‐Baseline Floating macroAlgae Height (VB‐FAH) index and OTSU threshold automatic segmentation algorithm to extract the area of PBs in Lake Dianchi, China, which has been subjected to frequent PBs and rapid urbanization in its vicinity. We further explored long‐term (2000–2021) trends in the phenological and severity metrics of PBs and quantified the contributions from urbanization, climate change, and also nutrient levels to these trends. When comparing data from 2011–2021 to 2000–2010, we found significantly advanced initiation of PBs (28.6 days) and noticeably longer duration (51.9 days) but an insignificant trend in time of disappearance. The enhancement of algal nutrient use efficiency, likely induced by increased water temperature and reduced nutrient concentrations, presumably contributed to an earlier initiation and longer duration of PBs, while there was a negative correlation between spring wind speed and the initiation of PBs. Fortunately, we found that both the area of the PBs and the frequency of severe blooms (covering more than 19.8 km 2 ) demonstrated downward trends, which could be attributed to increased wind speed and/or reduced nutrient levels. Moreover, the enhanced land surface temperature caused by urbanization altered the thermodynamic characteristics between the land and the lake, which, in turn, possibly caused an increase in local wind speed and water temperature, suggesting that urbanization can differently regulate the phenology and severity of PBs. Our findings have significant implications for the understanding of the impacts of urbanization on PB dynamics and for improving lake management practices to promote sustainable urban development under global change.

Molecular-level exploration of properties of dissolved organic matter in natural and engineered water systems: A critical review of FTICR-MS application - Mingqi Ruan; Fengchang Wu; Fuhong Sun; Fanhao Song; Tingting Li; Chen He; Juan Jiang (Critical Reviews in Environmental Science and Technology, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Fingerprint characteristics of refined oils and their traceability in the groundwater environment - Juan Sun; Xiaoyang Wang; Quanwei Song; Ran Li; Jiacai Xie; Xiaoqing Yang; Liuping Cai; Zihao Wang; Chaocheng Zhao; Xiuxia Zhang (Chemosphere, 2023)

A method to estimate leaf area index from VIIRS surface reflectance using deep transfer learning - Juan Li; Zhiqiang Xiao; Rui Sun; Jinling Song (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Changes in physicochemical characteristics and metabolites in the fermentation of goji juice by Lactiplantibacillus plantarum - Han Xie; Pengyan Gao; Zhen-Ming Lu; Fang-Zhou Wang; Li-Juan Chai; Jin-Song Shi; Hui-Ling Zhang; Yan Geng; Xiao-Juan Zhang; Zheng-Hong Xu (Food Bioscience, 2023)

Marine oil spill remediation by Candelilla wax modified coal fly ash cenospheres - Juan Sun; Ran Li; Xiaoyang Wang; Chaocheng Zhao; Quanwei Song; Fang Liu; Zihao Wang; Chunshuang Liu; Xiuxia Zhang (Chemosphere, 2023)

Alcohol induces apoptosis and autophagy in microglia BV-2 cells - Luchen Wang; Lingmin Song; Juan Ma; Huimei Wang; yingzhi Li; Danfei Huang (Food and Chemical Toxicology, 2023)

Isolation and characterization of a gas-producing and acid-resistant bacterium from spoiled vinegar - Xingjie Wang; Kaidi Hu; Fang Liu; Juan Mou; Jinghui Lai; Mengmei Zhang; Song Wang; Qin Li; Jianlong Li; Aiping Liu; Xiaolin Ao; Li He; et al. (International Journal of Food Microbiology, 2023)

Synergistic double doping of Co and Cu constructs multiple active sites to achieve catalyzed degradation of toluene at high humidity - Min Xu; Lei Wang; Yonggang Sun; Yulong Ma; Li Zhu; Yingbo Zhu; Juan Zhang; Song Qiao; Jingdan Gao; Wenxin Ji; Yuanyuan Li (Fuel, 2023)

Retraction Note: Ergosterol Attenuates Isoproterenol-Induced Myocardial Cardiotoxicity - Qifei Xie; Suiji Li; Yun Gao; Ling Jin; Cuilian Dai; Juan Song (Cardiovascular Toxicology, 2023)

Overestimation of 1O2 role in N-doped carbon materials/peroxymonosulfate system: The misleading of furfuryl alcohol quenching effect - Liangjie Wang; Juan Li; Xinyao Liu; Jiali Zhang; Ping Zeng; Yonghui Song (Chemosphere, 2023)

Machine learning based age-authentication assisted by chemo-kinetics: Case study of strong-flavor Chinese Baijiu - Qing-Ru Liu; Xiao-Juan Zhang; Lei Zheng; Lian-Jun Meng; Guang-Qian Liu; Ting Yang; Zhen-Ming Lu; Li-Juan Chai; Song-Tao Wang; Jin-Song Shi; Cai-Hong Shen; Zheng-Hong Xu (Food Research International, 2023)

Visual detection of Staphylococcus aureus based on immunomagnetic separation and polymerase spiral reaction - Yue Zhai; Haoyan Yu; Xingxing Liu; Mengfan Zhang; Rongpeng Han; Caihong Yin; Xingchi Liu; Hui Li; Juan Li; Xiuling Song (Food Control, 2023)

Characterization of RING-type ubiquitin SINA E3 ligases and their responsive expression to salt and osmotic stresses in Brassica napus - Fengyan Fang; Wenlong Zhou; Yanfeng Liu; Zhizhong Song; Songfeng Zheng; Fei Wang; Zeyu Lu; Dazhuang Qi; Bei Li; Nan Sun; Xiaoli Tang; Juan Zhang; et al. (Plant Cell Reports, 2023)

Metabolomics analysis reveals cytotoxic effects of ouabain towards psoriatic keratinocytes via impairment of glutathione metabolism - Xuan Zhou; Fei Fei; Wei Song; Hehua Ma; Zhenzhen Xu; Jing Yue; Bei Cao; Runbin Sun; Yu Zhao; Yuanxun Yang; Junyi Jiang; Yan Geng; et al. (Molecular Genetics and Genomics, 2023)
Ouabain is a cardiac glycoside long studied for treating heart diseases, but the attempts to evaluate its anti-psoriatic activity have not been reported. We aimed to explore the effects of ouabain on proliferation and metabolism towards psoriatic keratinocytes. In human HaCaT keratinocytes, ouabain potently decreased viability, promoted apoptosis and caused G2/M cycle arrest. Metabolomics analysis indicated that ouabain markedly impaired glutathione metabolism. The solute carrier family 7 member 11 (SLC7A11) is an amino acid transporter highly specific to cysteine, which is critical for glutathione synthesis. Ouabain downregulated SLC7A11, reduced cysteine uptake and subsequently inhibited glutathione synthesis, probably through inhibiting Akt/mTOR/beclin axis that regulate protein activity of SLC7A11. The impaired glutathione synthesis and oxidative stress caused by ouabain may contribute to its cytotoxicity towards psoriatic keratinocytes. Our results provide experimental evidence supporting further study of ouabain as a potential anti-psoriatic agent.

Triple signal amplification strategy for ultrasensitive in situ imaging of intracellular telomerase RNA - Juan Song; Shan Li; Jie Zhou; Qiao Yu; Xue-Jiao Yang; Hong-Yuan Chen; Jing-Juan Xu (Analytica Chimica Acta, 2023)

Characterization and identification of grapevine heat stress-responsive microRNAs revealed the positive regulated function of vvi-miR167 in thermostability - Lipeng Zhang; Dongying Fan; Hui Li; Qiuju Chen; Zhen Zhang; Minying Liu; Jingjing Liu; Yue Song; Juan He; Wenping Xu; Shiren Song; Huaifeng Liu; et al. (Plant Science, 2023)

Bacteria and filamentous fungi running a relay race in Daqu fermentation enable macromolecular degradation and flavor substance formation - Wen-Hu Liu; Li-Juan Chai; Hong-Mei Wang; Zhen-Ming Lu; Xiao-Juan Zhang; Chen Xiao; Song-Tao Wang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (International Journal of Food Microbiology, 2023)

N-acetylcysteine promotes the proliferation of porcine adipose-derived stem cells during in vitro long-term expansion for cultured meat production - Wen-Juan Song; Pei-Pei Liu; Zi-Qing Meng; Shi- Jie Ding; Hui- Xia Li (Food Research International, 2023)

Relationships between the Hadley circulation and tropical sea surface temperature with different meridional structures simulated in CMIP6 models - Yan Li; Mengying Du; Juan Feng; Falei Xu; Wenjun Song (Frontiers in Marine Science, 2023)
The variability of the Hadley Circulation (HC) is greatly impacted by the meridional structure of sea surface temperature (SST), which has varied effects depending on its symmetrical or asymmetrical pattern relative to the equator. By using the Coupled Comparison Program International Project Phase 6 (CMIP6) model outputs and reanalysis datasets, this study assesses the capacity of CMIP6 models to simulate the relationship between the HC and tropical SST under different meridional structures, as well as investigates the possible causes for simulation biases. It is shown that the CMIP6 models can successfully reproduce climatological HC, tropical SST, and their spatial patterns of first leading modes under different meridional structures, where the correlation coefficient between simulations and observations reaches 0.8 or above. By comparison, the CMIP6 model outputs exhibit substantial differences in simulating the HC to SST response over the different meridional structures, with obvious inter-model differences. Considering the capability in simulating the HC to tropical SST response, the CMIP6 models are divided into two types, Type I model and Type II model. Models of Type I are those whose simulation results are basically close to the reanalysis data, with the biases being less than 20%. The models of Type II are those whose simulated response ratios are much stronger than those of the reanalysis. It is found that the models of Type II overestimate the intensity of El Niño-Southern Oscillation (ENSO) events, and remarkably underestimate the HC and SST correlation in the equatorial symmetric part, resulting in the inability of the models of Type II to capture the connection of the HC and tropical SST. The results indicate that, the component of the CMIP6 models in reproducing the ENSO events has a considerable impact on the simulation of the HC and tropical SST relationship, which offers recommendations for enhancing the capability of models to simulate large-scale tropical air-sea interactions.

Isomer-specific perfluoroalkyl acids accumulation, excretion and maternal transfer to eggs in chickens around a fluorochemical manufactory in China - Yan Gao; Boyu Song; Anen He; Chao Liu; Yao Lu; Juan Li; Jianjie Fu; Yong Liang; Yawei Wang (Science of The Total Environment, 2023)

Evaluation the food safety of cultured fat via detection of residues of adipogenic differentiation cocktail in cultured fat with high performance liquid chromatography and enzyme-linked immunosorbent assay - Wen-Juan Song; Pei-Pei Liu; Chun-Bao Li; Hui- Xia Li; Shi- Jie Ding; Guang-Hong Zhou (Food Research International, 2023)

Where does the runoff come from in dry season in the source region of the Yangtze River? - Li Zongjie; Liu Mengqing; Li Zongxing; Feng Qi; Song Ling-Ling; Xu Bin; Liu Xiaoying; Gui Juan (Agricultural and Forest Meteorology, 2023)

Oxidative treatment of NOM by selective oxidants in drinking water treatment and its impact on DBP formation in postchlorination - Juan Li; Yang Song; Jin Jiang; Tao Yang; Ying Cao (Science of The Total Environment, 2023)

Diverse undescribed compounds from the rhizome of Zingiber officinale Rosc. And their anti-inflammatory activity - Xiao-Juan Zhang; Ze-Zhi Li; Zhi-Min Song; Yue-Tong Zhu; Wei-Sheng Feng; Yong-Xian Cheng; Yan-Zhi Wang (Phytochemistry, 2023)

Sodium Para-Aminosalicylic Acid Modulates Autophagy to Lessen Lead-Induced Neurodegeneration in Rat Cortex - Lei-lei Wang; Xiao-juan Zhu; Yuan-yuan Fang; Yan Li; Yue-song Zhao; Cui-liu Gan; Jing-jing Luo; Shi-yan Ou; Michael Aschner; Yue-ming Jiang (Neurotoxicity Research, 2023)

Alternations of interhemispheric functional connectivity in patients with optic neuritis using voxel-mirrored homotopic connectivity: A resting state fMRI study - Ke Song; Ya-Li Lv; Li-juan Yang; Peng Lv; Bo Ren; Jun Tian; Dao-qing Wei; Huan Li; Yi Shao (Brain Imaging and Behavior, 2023)

Using colloidal AFM probe technique and XDLVO theory to predict the transport of nanoplastics in porous media - Li-Juan Feng; Zong-Lin Shi; Jian-Lu Duan; Yi Han; Xiao-Dong Sun; Jing-Ya Ma; Xiao-Yu Liu; Huan-Xin Zhang; Ning Guo; Chao Song; Wan-Song Zong; Xian-Zheng Yuan (Chemosphere, 2023)

Impact of air pollutants on influenza-like illness outpatient visits under urbanization process in the sub-center of Beijing, China - Zhong-Song Zhang; Lu Xi; Li-Li Yang; Xin-Yao Lian; Juan Du; Yan Cui; Hong-Jun Li; Wan-Xue Zhang; Chao Wang; Bei Liu; Yan-Na Yang; Fuqiang Cui; et al. (International Journal of Hygiene and Environmental Health, 2023)

Thermodynamic characteristics of methane hydrate formation in high-pressure microcalorimeter under different reaction kinetics - Juan Fu; Jia-Mei Mo; Shi-Jun Liu; Wen-Zhe Yi; Yi-Song Yu; Neng-You Wu; Xiao-Li Chen; Qiu-Cheng Su; Xiao-Sen Li (Fuel, 2023)

Recycle waste washcloth to design Fe3O4/FeS2/C heterojunction membrane as high-area capacity freestanding anode for sodium-ion batteries - Qing Lin; Shaocheng Zhang; Li-Juan Yu; Baoxiu Hou; Shuaihua Zhang; Zheng Wang; Jianjun Song; Xiaoxian Zhao (Chemical Engineering Journal, 2023)

The protection effect of rhodionin against methicillin-resistant Staphylococcus aureus-induced pneumonia through sortase A inhibition - Xingye Wang; Yanhe Luan; Juan Hou; Tao Jiang; Yicheng Zhao; Wu Song; Li Wang; Xiangri Kong; Jiyu Guan; Danning Song; Bingmei Wang; Mingquan Li (World Journal of Microbiology and Biotechnology, 2023)

An inhibitory effect of schisandrone on α-hemolysin expression to combat methicillin-resistant staphylococcus aureus infections - Yingxin Qi; Juan Hou; Yicheng Zhao; Wu Song; Li Wang; Huan Chen; Guang Chen (World Journal of Microbiology and Biotechnology, 2023)

Drug-induced microglial phagocytosis in multiple sclerosis and experimental autoimmune encephalomyelitis and the underlying mechanisms - Wen-Yuan Ju; Qing Wang; Li-Juan Song; Zhi-Bin Ding; Xiao-Hui Li; Gajendra Kumar; Yuqing Yan; Cun-Gen Ma (Molecular Biology Reports, 2023)

Structural development of the nutrient transfer tissues in different waxy wheat grain - Juan Liu; Yuangang Zhu; Mingyue Xian; Liang Shen; Yan Li; Jian Song; Zhongmin Dai (Cereal Research Communications, 2022)

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Trace element signature of hydrothermal quartz: a potential tracer for ore genesis - Juan Dong; Li-Bin Jia; Mei-jia Song; Shu-Teng Xu; Mao-Wen Yuan; Cheng-Lu Li; Yuan-Jiang Yang (Arabian Journal of Geosciences, 2022)

Efficient removal of microplastics from aqueous solution by a novel magnetic biochar: performance, mechanism, and reusability - Juanjuan Wu; Chan Yang; Hanghang Zhao; Juan Shi; Zhifeng Liu; Chen Li; Fengmin Song (Environmental Science and Pollution Research, 2022)

Functional divergence of oligoadenylate synthetase 1 (OAS1) proteins in Tetrapods - Xiaoxue Wang; Jiaxiang Hu; Linfei Song; Enguang Rong; Chenghuai Yang; Xiaoyun Chen; Juan Pu; Honglei Sun; Chuze Gao; David W. Burt; Jinhua Liu; Ning Li; et al. (Science China Life Sciences, 2022)

Ambient temperature exposure and risk of outpatient visits for dermatologic diseases in Xinxiang, China: a time-series analysis - Ling Chao; Mengxue Lu; Wenshan Gao; Zhen An; Juan Li; Yue Liu; Weidong Wu; Jie Song (International Journal of Biometeorology, 2022)

Wuzi Yanzong pill attenuates MPTP-induced Parkinson’s Disease via PI3K/Akt signaling pathway - Wei Hang; Hui-jie Fan; Yan-rong Li; Qi Xiao; Lu Jia; Li-juan Song; Yao Gao; Xiao-ming Jin; Bao-guo Xiao; Jie-zhong Yu; Cun-gen Ma; Zhi Chai (Metabolic Brain Disease, 2022)

Identification and management of GCK-MODY complicating pregnancy in Chinese patients with gestational diabetes - Yanyan Jiang; Fusong Jiang; Ming Li; Qingkai Wu; Chenming Xu; Rong Zhang; Mingqiang Song; Yanzhong Wang; Ying Wang; Yating Chen; Juan Zhang; Xiaoxu Ge; et al. (Molecular and Cellular Biochemistry, 2022)

Distinct assembly mechanisms of microbial sub-communities with different rarity along the Nu River - Song Zhang; Kexin Li; Jinming Hu; Fang Wang; Danhong Chen; Zejin Zhang; Ting Li; Linfeng Li; Juan Tao; Dong Liu; Rongxiao Che (Journal of Soils and Sediments, 2022)

The genes for sensory perception of sound should be considered in gene diagnosis of congenital sensorineural hearing loss and microtia - Ken Lin; Ding-Yun You; Li-Huan Zhang; Li-Juan Zhou; Jin-Yan Zu; Yang Xiao; Mei-Hua Sun; Dong-Su; Xue Cao; Tie-Song Zhang; Jing Ma (Journal of Applied Genetics, 2022)

Two new dammarane-type triterpenoids from the green walnut husks of Juglans mandshurica Maxim - Yuan-Yuan Zhou; Hui-Rui Gao; Hong-Juan Song; Dan-Da Ma; Xiao-Juan Zhang; Yan-Ping Sun; Yan Liu; Xiao-Li Wang; Bing-You Yang; Hai-Xue Kuang (Natural Product Research, 2022)

Distinct co-occurrence patterns and driving forces of abundant and rare bacterial communities in the multispecies solid-state fermentation process of cereal vinegar - Ming-Ye Peng; Zhen-Ming Lu; Xiao-Juan Zhang; Ting Huang; Yong-Jian Deng; Li-Juan Chai; Jin-Song Shi; Zheng-Hong Xu (Systems Microbiology and Biomanufacturing, 2022)

Follicular Fluid-Derived Exosomal MicroRNA-18b-5p Regulates PTEN-Mediated PI3K/Akt/mTOR Signaling Pathway to Inhibit Polycystic Ovary Syndrome Development - Zhi Zhou; Zhihua Tu; Juan Zhang; Can tan; Xiaoyong Shen; Bangbei Wan; Yejuan Li; Anguo Wang; Liqiang Zhao; Jiajia Hu; Ning Ma; Jing Zhou; et al. (Molecular Neurobiology, 2022)

Pollution characteristics and emissions of typical organophosphate esters of a wastewater treatment plant - Hongling Yin; Yi Luo; Jiaojiao Song; Shiping Li; Shuyu Lin; Yuanming Xiong; Shuhong Fang; Juan Tang (Environmental Science and Pollution Research, 2022)

Hydrochemical patterns indicating hydrological processes with the background of changing climatic and environmental conditions in China: a review - Li Zong-Jie; Song Ling-Ling; Gui Juan; Li Zong-Xing (Environmental Science and Pollution Research, 2022)

Effects of ambient temperature on outpatient visits for dermatitis in Xinxiang, China: a time-series analysis - Ling Chao; Yajun Sun; Zhen An; Juan Li; Weidong Wu; Yue Liu; Jie Song (Environmental Science and Pollution Research, 2022)

A 250 m resolution global leaf area index product derived from MODIS surface reflectance data - Zhiqiang Xiao; Jinling Song; Hua Yang; Rui Sun; Juan Li (International Journal of Remote Sensing, 2022)

Autophagy Inhibition Reduces Irradiation-Induced Subcortical White Matter Injury Not by Reducing Inflammation, but by Increasing Mitochondrial Fusion and Inhibiting Mitochondrial Fission - Yafeng Wang; Yiran Xu; Kai Zhou; Shan Zhang; Yong Wang; Tao Li; Cuicui Xie; Xiaoli Zhang; Juan Song; Xiaoyang Wang; Changlian Zhu (Molecular Neurobiology, 2022)
Radiotherapy is an effective tool in the treatment of malignant brain tumors, but irradiation-induced late-onset toxicity remains a major problem. The purpose of this study was to investigate if genetic inhibition of autophagy has an impact on subcortical white matter development in the juvenile mouse brain after irradiation. Ten-day-old selective neural Atg7 knockout (KO) mice and wild-type (WT) littermates were subjected to a single 6-Gy dose of whole-brain irradiation and evaluated at 5 days after irradiation. Neural Atg7 deficiency partially prevented myelin disruption compared to the WT mice after irradiation, as indicated by myelin basic protein staining. Irradiation induced oligodendrocyte progenitor cell loss in the subcortical white matter, and Atg7 deficiency partly prevented this. There was no significant change between the KO and WT mice in the number of microglia and astrocytes in the subcortical white matter after irradiation. Transcriptome analysis showed that the GO mitochondrial gene expression pathway was significantly enriched in the differentially expressed genes between the KO and WT group after irradiation. Compared with WT mice, expression of the mitochondrial fusion protein OPA1 and phosphorylation of the mitochondrial fission protein DRP1 (P-DRP1) were dramatically decreased in KO mice under physiological conditions. The protein levels of OPA1and P-DRP1 showed no differences in WT mice between the non-irradiated group and the irradiated group but had remarkably increased levels in the KO mice after irradiation. These results indicate that inhibition of autophagy reduces irradiation-induced subcortical white matter injury not by reducing inflammation, but by increasing mitochondrial fusion and inhibiting mitochondrial fission.

East Asian summer monsoon changes in subtropical China since late Pleistocene: Evidence from the Ailuropoda-Stegodon fauna - Zhi-wen Li; Li Sun; Bao-sheng Li; Feng-nian Wang; Ding-ding Du; You-gui Song; Hui-Juan Zhang; Liu-qin Chen; Dan Xu (Journal of Mountain Science, 2022)

Distinct durability of IgM/IgG antibody responses in COVID-19 patients with differing severity - Junyan Han; Ning Zhang; Danying Chen; Yuhuan Gong; Guoli Li; Yaxian Kong; Lin Pu; Chen Chen; Jingyuan Liu; Qi Wang; Ju Zhang; Xuesen Zhao; et al. (Science China Life Sciences, 2022)

Classification of electrocardiogram signals with waveform morphological analysis and support vector machines - Hongqiang Li; Zhixuan An; Shasha Zuo; Wei Zhu; Lu Cao; Yuxin Mu; Wenchao Song; Quanhua Mao; Zhen Zhang; Enbang Li; Juan Daniel Prades García (Medical & Biological Engineering & Computing, 2022)

Soil moisture response to land use and topography across a semi-arid watershed: Implications for vegetation restoration on the Chinese Loess Plateau - Lu Xia; Ru-tian Bi; Xiao-yu Song; Wei Hu; Chun-juan Lyu; Xu Xi; Huai-you Li (Journal of Mountain Science, 2022)

Nakamurella leprariae sp. nov., isolated from a lichen sample - De-Feng An; Shao-Juan Yang; Long-Qian Jiang; Xin-Yu Wang; Xiao-Yu Huang; Lei Lang; Xue-Mei Chen; Ming-Qun Fan; Gui-Ding Li; Ming-Guo Jiang; Li-Song Wang; Cheng-Lin Jiang; et al. (Archives of Microbiology, 2022)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Recent progress of oridonin and its derivatives for cancer therapy and drug resistance - Yong-Feng Guan; Xiu-Juan Liu; Xiao-Jing Pang; Wen-Bo Liu; Guang -Xi Yu; Yin -Ru Li; Yan-Bing Zhang; Jian Song; Sai-Yang Zhang (Medicinal Chemistry Research, 2021)

24-epibrassinolide improves differential cadmium tolerance of mung bean roots, stems, and leaves via amending antioxidative systems similar to that of abscisic acid - Ya-Juan Song; Yi Li; Yan Leng; Shi-Weng Li (Environmental Science and Pollution Research, 2021)

The effects of biochar/compost for adsorption behaviors of sulfamethoxazole in amended wetland soil - Siqun Tang; Jie Liang; Jilai Gong; Biao Song; Zhaoxue Yang; Siyuan Fang; Peng Zhang; Weicheng Cao; Juan Li; Yuan Luo (Environmental Science and Pollution Research, 2021)

Short-term effect of NO2 on outpatient visits for dermatologic diseases in Xinxiang, China: a time-series study - Ling Chao; Mengxue Lu; Zhen An; Juan Li; Yuchun Li; Qian Zhao; Yinbiao Wang; Yue Liu; Weidong Wu; Jie Song (Environmental Geochemistry and Health, 2021)

Different posterior hippocampus and default mode network modulation in young APOE ε4 carriers: a functional connectome-informed phenotype longitudinal study - Li Juan Zheng; Li Lin; U. Joseph Schoepf; Akos Varga-Szemes; Rock H. Savage; Han Zhang; Yun Fei Wang; Xin Yuan Zhang; Song Luo; Ya Liu; Gui Fen Yang; Guang Ming Lu; et al. (Molecular Neurobiology, 2021)

Effects of prenatal exposure to bisphenols on newborn leucocyte telomere length: a prospective birth cohort study in China - Jun Liang; Yantao Shao; Dongping Huang; Chunxiu Yang; Tao Liu; Xiaoyun Zeng; Chunling Li; Zhenghua Tang; Jennifer Tan Hui Juan; Yanye Song; Shun Liu; Xiaoqiang Qiu (Environmental Science and Pollution Research, 2021)

Low-Dose Triptolide Enhanced Activity of Idarubicin Against Acute Myeloid Leukemia Stem-like Cells Via Inhibiting DNA Damage Repair Response - Pengcheng Shi; Jie Zha; Juan Feng; Zhiwu Jiang; Haijun Zhao; Manman Deng; Naying Liao; Peng Li; Yirong Jiang; Haihan Song; Bing Xu (Stem Cell Reviews and Reports, 2021)

Global patterns in leaf stoichiometry across coastal wetlands - Yu‐Kun Hu; Xu‐Yan Liu; Nian‐Peng He; Xu Pan; Song‐Yuan Long; Wei Li; Man‐Yin Zhang; Li‐Juan Cui (Global Ecology and Biogeography, 2021)
Aim Coastal wetlands provide crucial ecosystem functions and services, such as coastal protection, nutrient retention and C sequestration. Despite the important roles in global C, N and P cycling, the global variation in leaf stoichiometry across coastal wetlands remains unclear. Location Global. Time period 1980–2018. Major taxa studied Vascular plants. Methods By compiling a global dataset of 698 data records in 205 sites, we carried out systematic analyses of the world‐wide trends and their determinants of leaf element contents and ratios of plants across coastal wetlands. Results Leaf N and P contents increased significantly, but C:N, C:P and N:P ratios decreased with increasing latitude in coastal wetlands. The mean annual temperature was the predominant driver of leaf N, P and C:N, whereas soil N:P was a good predictor of leaf C:P and N:P ratios. Furthermore, N increased faster with P in plant leaves of coastal wetlands compared with terrestrial ecosystems. Within coastal wetlands, herb‐dominated salt marshes had a significantly higher leaf P content, lower leaf N:P ratio and lower scaling exponent of leaf N to P than tree‐dominated mangroves. Main conclusions The similar latitudinal patterns of leaf stoichiometry in coastal wetlands compared with terrestrial ecosystems reflected the similar influences of temperature. However, different slopes of leaf P and N:P ratios and N and P scaling relationships between these two ecosystems suggested that different salinity and tidal inundation levels result in different strategies of N and P use in coastal wetland plants. These differences in leaf stoichiometry between ecosystems and between different types of coastal wetlands might need to be emphasized in future biogeochemical modelling owing to their different roles in global nutrient and carbon cycling.

Acute effects of ambient air pollution on outpatients with chronic rhinitis in Xinxiang, China - Mengxue Lu; Huijuan Yang; Jingyao Wang; Zhen An; Juan Li; Zhineng Wu; Qian Zhao; Huijun Li; Desheng Zhai; Yue Liu; Weidong Wu; Jie Song (Environmental Science and Pollution Research, 2021)

Partial recovery of disturbed V-J pairing profiles of T-cell receptor in people living with HIV receiving long-term antiretroviral therapy - Guoli Li; Jiarui Li; Henghui Zhang; Yu Zhang; Di Liu; Yu Hao; Junyan Han; Juan Du; Liuluan Zhu; Yongqin Zeng; Bei Li; Rui Li; et al. (Science China Life Sciences, 2021)

A forecasting model for wave heights based on a long short-term memory neural network - Song Gao; Juan Huang; Yaru Li; Guiyan Liu; Fan Bi; Zhipeng Bai (Acta Oceanologica Sinica, 2021)

Using sowing date management to promote micronutrient quality and alleviate cadmium accumulation in rice grains - Lin-lin Shi; Ming-xing Shen; Hong-jun Wu; Chang-ying Lu; Li-juan Mei; Xin-lian Zhu; Hai-hou Wang; Yun-Sheng Song (Cereal Research Communications, 2020)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Effect analysis of borehole microseismic monitoring technology on shale gas fracturing in western Hubei - Juan Li; Bing-Song Yu; Yu-Kun Tian; Hai-Xia Kang; Yu-Fang Wang; Hui Zhou (Applied Geophysics, 2020)

Acute effects of ambient air pollution on hospital outpatients with chronic pharyngitis in Xinxiang, China - Xiangmei Zhao; Mengxue Lu; Zhen An; Juan Li; Huijun Li; Qian Zhao; Zhineng Wu; Weidong Wu; Yue Liu; Jie Song (International Journal of Biometeorology, 2020)

Highly sensitive serological approaches for Pepino mosaic virus detection - Wan-qin He; Jia-yu Wu; Yi-yi Ren; Xue-ping Zhou; Song-bai Zhang; Ya-juan Qian; Fang-fang Li; Jian-xiang Wu (Journal of Zhejiang University-SCIENCE B, 2020)

RETRACTED ARTICLE: Ergosterol Attenuates Isoproterenol-Induced Myocardial Cardiotoxicity - Qifei Xie; Suiji Li; Yun Gao; Ling Jin; Cuilian Dai; Juan Song (Cardiovascular Toxicology, 2020)

Adsorption and Desorption Characteristics of Vanadium (V) on Coexisting Humic Acid and Silica - Qiao-yu Song; Meng Liu; Juan Lu; Yu-liang Liao; Li Chen; Jin-yan Yang (Water, Air, & Soil Pollution, 2020)

A new bis-γ-pyrone polypropionate of onchidiol family from marine pulmonate mollusk Onchidium sp - Song-Wei Li; Wan-Xiang Cui; Xia-Juan Huan; Margherita Gavagnin; Ernesto Mollo; Ze-Hong Miao; Li-Gong Yao; Xu-Wen Li; Yue-Wei Guo (Natural Product Research, 2020)

Identification of Ala2Thr mutation in insulin gene from a Chinese MODY10 family - Juan Zhang; Yanjun Liu; Ming Li; Xiaoxu Ge; Ying Wang; Xin Huang; Di Yang; Rong Zhang; Yating Chen; Ming Lu; Jun Yin; Mingqiang Song; et al. (Molecular and Cellular Biochemistry, 2020)

Associations between air pollution and outpatient visits for allergic rhinitis in Xinxiang, China - Jingyao Wang; Mengxue Lu; Zhen An; Jing Jiang; Juan Li; Yinbiao Wang; Shuang Du; Xuexing Zhang; Haofeng Zhou; Juan Cui; Weidong Wu; Yue Liu; et al. (Environmental Science and Pollution Research, 2020)

The research trends of metal-organic frameworks in environmental science: a review based on bibliometric analysis - Juan Li; Liangjie Wang; Yongqiang Liu; Yonghui Song; Ping Zeng; Yajie Zhang (Environmental Science and Pollution Research, 2020)

Orogenic Movements during the Paleozoic Period: Development of the Granitoid Formations in the Northwestern Region of Spain’s Iberian Peninsula - Juan Ramon Vidal Romaní; Zhaojun Song; Huimin Liu; Yifang Sun; Haonan Li (Journal of Earth Science, 2020)

Using probiotics for type 2 diabetes mellitus intervention: Advances, questions, and potential - Zhongke Sun; Xuejiao Sun; Juan Li; Zhaoyang Li; Qingwei Hu; Lili Li; Xinqi Hao; Maoping Song; Chengwei Li (Critical Reviews in Food Science and Nutrition, 2020)

The Rho kinase inhibitor fasudil attenuates Aβ1–42-induced apoptosis via the ASK1/JNK signal pathway in primary cultures of hippocampal neurons - Ye Gao; Yuqing Yan; Qingli Fang; Nianping Zhang; Gajendra Kumar; Jihong Zhang; Li-Juan Song; Jiezhong Yu; Linhu Zhao; Han-Ting Zhang; Cun-Gen Ma (Metabolic Brain Disease, 2019)

Angiotensin II induces apoptosis of cardiac microvascular endothelial cells via regulating PTP1B/PI3K/Akt pathway - Yanyan Wang; Yuyuan Fan; Yu Song; Xueting Han; Mingqiang Fu; Jingfeng Wang; Xiaotong Cui; Juan Cao; Li Chen; Kai Hu; Aijun Sun; Jingmin Zhou; et al. (In Vitro Cellular & Developmental Biology - Animal, 2019)

A cross-sectional survey based on blood VOCs, hematological parameters and urine indicators in a population in Jilin, Northeast China - Xiaocui Li; Yuanyuan Guo; Xiuling Song; Yinghua He; Huiwen Zhang; Hao Bao; Xinxin Li; Yushen Liu; Yue Zhai; Juan Wang; Kun Xu; Juan Li (Environmental Geochemistry and Health, 2019)

Intravitreal Ets1 siRNA alleviates choroidal neovascularization in a mouse model of age-related macular degeneration - Manhui Zhu; Li Jiang; You Yuan; Lili Chen; Xiaojuan Liu; Juan Liang; Qiujian Zhu; Dongmei Ding; E. Song (Cell and Tissue Research, 2019)

Integrin-interacting protein Kindlin-2 induces mammary tumors in transgenic mice - Bing Li; Xiaochun Chi; Jiagui Song; Yan Tang; Juan Du; Xiaokun He; Xiaoran Sun; Zhenwu Bi; Yunling Wang; Jun Zhan; Hongquan Zhang (Science China Life Sciences, 2019)

A new12-membered lactone from the stems of Ficus auriculata - Tai-Ming Shao; Cai-Juan Zheng; Xiao-Bao Li; Guang-Ying Chen; Xiao-Ping Song; Chang-Ri Han (Natural Product Research, 2018)

Characterization of clinical features and outcome for human-to-human transmitted severe fever with thrombocytopenia syndrome - Bei Jia; Weihua Wu; Rui Huang; Guiyang Wang; Peixin Song; Yang Li; Yong Liu; Yali Xiong; Xiaomin Yan; Yingying Hao; Juan Xia; Zhaoping Zhang; et al. (Infectious Diseases, 2018)

Characterization of the complete sequences and stability of plasmids carrying the genes aac(6′)-Ib-cr or qnrS in Shigella flexneri in the Hangzhou area of China - Xiao-Ying Pu; Yaming Gu; Jun Li; Shu-Juan Song; Zhe Lu (World Journal of Microbiology and Biotechnology, 2018)

Mutation screening of Chinese Treacher Collins syndrome patients identified novel TCOF1 mutations - Ying Chen; Luo Guo; Chen-long Li; Jing Shan; Hai-song Xu; Jie-ying Li; Shan Sun; Shao-juan Hao; Lei Jin; Gang Chai; Tian-yu Zhang (Molecular Genetics and Genomics, 2018)

Biotoxicity of Cry1Ab protein on wolf spider Pardosa pseudoannulata - Juan Wang; Yuande Peng; Huilin Yang; Zhenzhen Yan; Qinjin Li; Yixue Shi; Chunliang Xie; Yunshan Liang; Zhi Wang; Qisheng Song (Ecotoxicology, 2017)

Population transcriptomic characterization of the genetic and expression variation of a candidate progenitor of Miscanthus energy crops - Juan Yan; Zhihong Song; Qin Xu; Lifang Kang; Caiyun Zhu; Shilai Xing; Wei Liu; Josef Greimler; Tobias Züst; Jianqiang Li; Tao Sang (Molecular Ecology, 2017)
The use of transcriptome data in the study of the population genetics of a species can capture faint signals of both genetic variation and expression variation and can provide a broad picture of a species’ genomic response to environmental conditions. In this study, we characterized the genetic and expression diversity of Miscanthus lutarioriparius by comparing more than 16,225 transcripts obtained from 78 individuals, belonging to 10 populations distributed across the species’ entire geographic range. We only observed a low level of nucleotide diversity (π = 0.000434) among the transcriptome data of these populations, which is consistent with highly conserved sequences of functional elements and protein‐coding genes captured with this method. Tests of population divergence using the transcriptome data were consistent with previous microsatellite data but proved to be more sensitive, particularly if gene expression variation was considered as well. For example, the analysis of expression data showed that genes involved in photosynthetic processes and responses to temperature or reactive oxygen species stimuli were significantly enriched in certain populations. This differential gene expression was primarily observed among populations and not within populations. Interestingly, nucleotide diversity was significantly negatively correlated with expression diversity within populations, while this correlation was positive among populations. This suggests that genetic and expression variation play separate roles in adaptation and population persistence. Combining analyses of genetic and gene expression variation represents a promising approach for studying the population genetics of wild species and may uncover both adaptive and nonadaptive processes.

A new biphenyl derivative from the mangrove endophytic fungus Phomopsis longicolla HL-2232 - Xiao-Bao Li; Guang-Ying Chen; Rui-Jie Liu; Cai-Juan Zheng; Xin-Ming Song; Chang-Ri Han (Natural Product Research, 2017)

Fasudil Enhances Therapeutic Efficacy of Neural Stem Cells in the Mouse Model of MPTP-Induced Parkinson’s Disease - Yan-Hua Li; Jing-Wen Yu; Jian-Yin Xi; Wen-Bo Yu; Jian-Chun Liu; Qing Wang; Li-Juan Song; Ling Feng; Ya-Ping Yan; Guang-Xian Zhang; Bao-Guo Xiao; Cun-gen Ma (Molecular Neurobiology, 2017)

Effect of phosphate additive on the nitrogen transformation during pig manure composting - Juan Wu; Shengzhou He; Ying Liang; Guoxue Li; Song Li; Shili Chen; Faisal Nadeem; Jingwei Hu (Environmental Science and Pollution Research, 2017)

Inhalation of Roman chamomile essential oil attenuates depressive-like behaviors in Wistar Kyoto rats - Yingying Kong; Ting Wang; Rong Wang; Yichuan Ma; Shanshan Song; Juan Liu; Weiwei Hu; Shengtian Li (Science China Life Sciences, 2017)

One new lignan derivative from the Combretum alfredii Hance - Meng Bai; Li-Jun Wu; Yue Cai; Shou-Yuan Wu; Xiao-Ping Song; Guang-Ying Chen; Cai-Juan Zheng; Chang-Ri Han (Natural Product Research, 2017)

Insulin-independent GLUT4 translocation in proliferative vascular smooth muscle cells involves SM22α - Li-Li Zhao; Fan Zhang; Peng Chen; Xiao-Li Xie; Yong-Qing Dou; Yan-Ling Lin; Lei Nie; Pin Lv; Dan-Dan Zhang; Xiao-Kun Li; Sui-Bing Miao; Ya-Juan Yin; et al. (Journal of Molecular Medicine, 2017)

Gastroprotective effect of palmatine against acetic acid-induced gastric ulcers in rats - Ling Wang; Xue Wang; Su-Li Zhang; Xiao-Ming Zhu; Yan-Qi Liu; Zi-Jing Song; Wen-Juan Du; Jun Ji; Cheng-Long Cui; Xin He; Chun-Feng Zhang; Chang-Run Guo; et al. (Journal of Natural Medicines, 2017)

Bone morphogenetic protein-2 sustained delivery by hydrogels with microspheres repairs rabbit mandibular defects - Wei-Yi Song; Guo-Min Liu; Juan Li; Yun-Gang Luo (Tissue Engineering and Regenerative Medicine, 2016)

One new berberine from the branches and leaves of Polyalthia obliqua Hook.f. & Thomson - Li-Jun Wu; Cai-Juan Zheng; Liu-Kai Wang; Chang-Ri Han; Xiao-Ping Song; Guang-Ying Chen; Xue-ming Zhou; Shou-yuan Wu; Xiao-bao Li; Meng Bai; Chun-xin Liu; Jun Yao (Natural Product Research, 2016)

Frequency of Spontaneous BOLD Signal Differences between Moderate and Late Preterm Newborns and Term Newborns - Xiushuang Wu; Luqing Wei; Nan Wang; Zhangxue Hu; Li Wang; Juan Ma; Shuai Feng; Yue Cai; Xiaopeng Song; Yuan Shi (Neurotoxicity Research, 2016)

Application of TiO2-organobentonite modified by cetyltrimethylammonium chloride photocatalyst and polyaluminum chloride coagulant for pretreatment of aging landfill leachate - Yi-Jie Zhang; Zhao-Hui Yang; Pei-Pei Song; Hai-Yin Xu; Rui Xu; Jing Huang; Juan Li; Yan Zhou (Environmental Science and Pollution Research, 2016)

Cerebral blood flow changes in hemodialysis and peritoneal dialysis patients: an arterial-spin labeling MR imaging - Xiao Lu Jiang; Ji Qiu Wen; Long Jiang Zhang; Gang Zheng; Xue Li; Zhe Zhang; Ya Liu; Li Juan Zheng; Long Wu; Hui Juan Chen; Xiang Kong; Song Luo; et al. (Metabolic Brain Disease, 2016)

Reverse transcription genome exponential amplification reaction assay for rapid and universal detection of human rhinoviruses - Li Guan; Lin-Qing Zhao; Hang-Yu Zhou; Kai Nie; Xin-Na Li; Dan Zhang; Juan Song; Yuan Qian; Xue-Jun Ma (Archives of Virology, 2016)

Improvement of soybean transformation via Agrobacterium tumefaciens methods involving α-aminooxyacetic acid and sonication treatments enlightened by gene expression profile analysis - Yan-Min Zhang; Zi-Hui Liu; Rui-Juan Yang; Guo-Liang Li; Xiu-Lin Guo; Hua-Ning Zhang; Hong-Mei Zhang; Rui Di; Qing-Song Zhao; Meng-Chen Zhang (Plant Cell Reports, 2016)

Combinatorial enzymatic digestion with thermolysin and collagenase type I improved the isolation and culture effects of hair cell progenitors from rat cochleae - Yong-li Song; Ke-yong Tian; Wen-juan Mi; Peng Han; Zhong-jia Ding; Yang Qiu; Fu-quan Chen; Jian-jua Qiu (In Vitro Cellular & Developmental Biology - Animal, 2016)

Spatial Variations of Soil Microbial Activities in Saline Groundwater-Irrigated Soil Ecosystem - Li-Juan Chen; Qi Feng; Chang-Sheng Li; You-Xi Song; Wei Liu; Jian-Hua Si; Bao-Gui Zhang (Environmental Management, 2016)

The SIRT1 inhibitor, nicotinamide, inhibits hepatitis B virus replication in vitro and in vivo - Wan-Yu Li; Ji-Hua Ren; Na-Na Tao; Long-Kuan Ran; Xiang Chen; Hong-Zhong Zhou; Bo Liu; Xiao-Song Li; Ai-Long Huang; Juan Chen (Archives of Virology, 2016)

Breeding of an intraspecific kelp hybrid Dongfang no. 6 (Saccharina japonica, Phaeophyceae, Laminariales) for suitable processing products and evaluation of its culture performance - Xiaojie Li; Zhuangzhi Zhang; Shancun Qu; Guangjin Liang; Nan Zhao; Juan Sun; Shaofeng Song; Zengmei Cao; Xia Li; Jinhua Pan; Shiju Luo; Linan Zhang; et al. (Journal of Applied Phycology, 2016)

Genome-wide analysis of the family 1 glycosyltransferases in cotton - Juan Huang; Chaoyou Pang; Shuli Fan; Meizhen Song; Jiwen Yu; Hengling Wei; Qifeng Ma; Libei Li; Chi Zhang; Shuxun Yu (Molecular Genetics and Genomics, 2015)

DNA methylation level of promoter region of activating transcription factor 5 in glioma - Xiao-min Hua; Juan Wang; Dong-meng Qian; Jing-yi Song; Hao Chen; Xiu-li Zhu; Rui Zhou; Yu-dan Zhao; Xiu-zhi Zhou; Ling Li; Li Zhang; Xu-xia Song; et al. (Journal of Zhejiang University-SCIENCE B, 2015)

Bacillus methylotrophicus isolated from the cucumber rhizosphere degrades ferulic acid in soil and affects antioxidant and rhizosphere enzyme activities - Yue Zhang; Xiu-Juan Wang; Shu-Yun Chen; Li-Yuan Guo; Ming-Lei Song; He Feng; Chen Li; Ji-Gang Bai (Plant and Soil, 2015)

Association between abortion and breast cancer: an updated systematic review and meta-analysis based on prospective studies - Jun Guo; Yubei Huang; Lei Yang; Zhengqiang Xie; Shuhong Song; Juan Yin; Li Kuang; Wengang Qin (Cancer Causes & Control, 2015)

Mycoremediation potential and tolerance responses of Oudemansiella radicata in cadmium-pyrene co-contaminated soil - Rong Chen; Zhiren Zhou; Yuanxiu Liu; Juan Jiang; Qiao Li; Haihai Song; Donghui Pei; Heng Xu (Journal of Soils and Sediments, 2015)

Ectopic expression of a phytochrome B gene from Chinese cabbage (Brassica rapa L. ssp. pekinensis) in Arabidopsis thaliana promotes seedling de-etiolation, dwarfing in mature plants, and delayed flowering - Mei-Fang Song; Shu Zhang; Pei Hou; Hong-Zhong Shang; Hai-Ke Gu; Jing-Juan Li; Yang Xiao; Lin Guo; Liang Su; Jian-Wei Gao; Jian-Ping Yang (Plant Molecular Biology, 2015)

Effect of a New Kind of Liquid Fertilizer on Yield, Quality and Safety of Greenhouse Chinese Cabbage - Na Song; Juan Wang; Qunhui Wang; Jin Zheng; Jie Chen; Shanshan Shi; Fasheng Li (Agricultural Research, 2015)

Geochronology and geochemistry of Grenville-aged (1063 ± 16 Ma) metabasalts in the Shennongjia district, Yangtze block: implications for tectonic evolution of the South China Craton - Xiao-Fei Qiu; Hong-Mei Yang; Shan-Song Lu; Wen-Li Ling; Li-Guo Zhang; Juan-Juan Tan; Zhi-Xian Wang (International Geology Review, 2015)

Design and applications of bifunctional cinnamide derivatives as potential antimycobacterial agents with few hepatotoxic effects - Zheng-Rong Wu; De-Juan Zhi; Li-Fang Zheng; Jian-Ying Li; Yang Li; Qing-Jian Xie; Na Feng; Yan-Fang Bao; Qi-Yu Gao; Ying Song; Hong-Yu Li (Medicinal Chemistry Research, 2015)

Two new cadinane-type sesquiterpenes from the Chinese liverwort Frullania serrata - Rui-Juan Li; Rong-Xiu Zhu; Yu Zhao; Susan L. Morris-Natschke; Chin-Ho Chen; Song Wang; Jiao-Zhen Zhang; Jin-Chuan Zhou; Hong-Xiang Lou; Kuo-Hsiung Lee (Natural Product Research, 2014)

The toxicity of cerium nitrate to Elodea canadensis: subcellular distribution, chemical forms and physiological effects - Wei Yue Chu; San Juan Cai; Yong Yang Fu; Fei Fei Li; Ting Xu; Han Qiu; Qin Song Xu (Acta Physiologiae Plantarum, 2014)

Assessment of dietary phytoestrogen intake via plant-derived foods in China - Xiao Juan Hu; Wan Rui Song; Li Ying Gao; Shao Ping Nie; Gerhard Eisenbrand; Ming Yong Xie (Food Additives & Contaminants: Part A, 2014)

Down-regulation of Gli-1 inhibits hepatocellular carcinoma cell migration and invasion - Jing-Song Chen; Hua-Shu Li; Jiong-Qiang Huang; Long-Juan Zhang; Xi-Lin Chen; Qian Wang; Jian Lei; Ju-Tao Feng; Qin Liu; Xiao-Hui Huang (Molecular and Cellular Biochemistry, 2014)

Effects of dominant microalgae species and bacterial quantity on shrimp production in the final culture season - Yu-cheng Cao; Guo-liang Wen; Zhuo-jia Li; Xiao-zhu Liu; Xiao-juan Hu; Jia-song Zhang; Jian-guo He (Journal of Applied Phycology, 2014)

Interferon-γ produced by tumor-infiltrating NK cells and CD4+ T cells downregulates TNFSF15 expression in vascular endothelial cells - Yi Lu; Xin Gu; Li Chen; Zhi Yao; Juan Song; Xiulong Niu; Rong Xiang; Tao Cheng; Zhihai Qin; Weimin Deng; Lu-Yuan Li (Angiogenesis, 2014)

Infection of Prions and Treatment of PrP106–126 Alter the Endogenous Status of Protein 14-3-3 and Trigger the Mitochondrial Apoptosis Possibly via Activating Bax Pathway - Qi Shi; Qin-Qin Song; Peng Sun; Jin Zhang; Juan Song; Li-Na Chen; Kang Xiao; Shao-Bin Wang; Ya-Zhou Zhang; Gong-Qi Li; Lin-Jun Sheng; Bao-Dong Wang; et al. (Molecular Neurobiology, 2014)

An approach based on antioxidant fingerprint–efficacy relationship and TLC bioautography assay to quality evaluation of Rubia cordifolia from various sources - Xu-Jie Zhang; Li-Juan Liu; Ting-Ting Song; Yan-Qiu Wang; Xiao-hong Yang (Journal of Natural Medicines, 2014)

Ovalbumin enhances YKL-40, IL-5, GM-CSF, and eotaxin expression simultaneously in primarily cultured mouse tracheal epithelial cells - Su-qin Ben; Ya-li Qiu; Juan Zhou; Xiao-yu Zhou; Shan Zhang; Yi Wu; Shao-qing Ju; Song-shi Ni (In Vitro Cellular & Developmental Biology - Animal, 2014)

Major QTLs reduce the deleterious effects of high temperature on rice amylose content by increasing splicing efficiency of Wx pre-mRNA - Hua Zhang; Lian Duan; Ji-Song Dai; Chang-Quan Zhang; Juan Li; Ming-Hong Gu; Qiao-Quan Liu; Ying Zhu (Theoretical and Applied Genetics, 2014)

Identification of a novel frameshift mutation in PITX2 gene in a Chinese family with Axenfeld-Rieger syndrome - Hou-Fa Yin; Xiao-Yun Fang; Chong-Fei Jin; Jin-Fu Yin; Jin-Yu Li; Su-Juan Zhao; Qi Miao; Feng-Wei Song (Journal of Zhejiang University-SCIENCE B, 2014)

Association of single-nucleotide polymorphisms in the STAT3 gene with autoimmune thyroid disease in Chinese individuals - Ling Xiao; Fatuma-Said Muhali; Tian-tian Cai; Rong-hua Song; Renming Hu; Xiao-hong Shi; Wen-juan Jiang; Dan-Feng Li; Shuang-tao He; Jian Xu; Jin-an Zhang (Functional & Integrative Genomics, 2013)

Effect of sulphate nutrition on arsenic translocation and photosynthesis of rice seedlings - Rui Song; Chen-Yun Zhao; Juan Liu; Jing Zhang; Yan-Xiu Du; Jun-Zhou Li; Hong-Zheng Sun; Hong-Bing Zhao; Quan-Zhi Zhao (Acta Physiologiae Plantarum, 2013)

Association between SNPs in microRNA-machinery genes and tuberculosis susceptibility in Chinese Tibetan population - Xingbo Song; Siyue Li; MeiLang QuCuo; Yi Zhou; Xin Hu; Juan Zhou; Xiaojun Lu; Jun Wang; Wei Hua; Yuanxin Ye; Binwu Ying; Lanlan Wang (Molecular Biology Reports, 2013)

Cytochrome P450 oxidoreductase genetic polymorphisms A503V and rs2868177 do not significantly affect warfarin stable dosage in Han-Chinese patients with mechanical heart valve replacement - Sheng-Lan Tan; Zhi Li; Wei Zhang; Guo-Bao Song; Li-Ming Liu; Juan Peng; Zhao-Qian Liu; Lan Fan; Xiang-Guang Meng; Lian-Sheng Wang; Yao Chen; Xin-Min Zhou; et al. (European Journal of Clinical Pharmacology, 2013)

β-Ionone arrests cell cycle of gastric carcinoma cancer cells by a MAPK pathway - Hong-Wei Dong; Shuang Zhang; Wen-Guang Sun; Qian Liu; Juan C. Ibla; Sulpicio G. Soriano; Xiao-Hui Han; Lian-Xin Liu; Ming-Song Li; Jia-Ren Liu (Archives of Toxicology, 2013)

Erratum to: Novel mutation c.980_983delATTA compound with c.986C>A mutation of the FRMD7 gene in a Chinese family with X-linked idiopathic congenital nystagmus - Feng-wei Song; Bin-bin Chen; Zhao-hui Sun; Li-ping Wu; Su-juan Zhao; Qi Miao; Xia-jing Tang (Journal of Zhejiang University-SCIENCE B, 2013)

QTL mapping and correlation analysis for 1000-grain weight and percentage of grains with chalkiness in rice - JIAN-MIN BIAN; HUAN SHI; CUI-JUAN LI; CHANG-LAN ZHU; QIU-YING YU; XIAO-SONG PENG; JUN-RU FU; XIAO-PENG HE; XIAO-RONG CHEN; LI-FANG HU; LIN-JUAN OUYANG; HAO-HUA HE (Journal of Genetics, 2013)

Novel mutation c.980_983delATTA compound with c.986C>A mutation of the FRMD7 gene in a Chinese family with X-linked idiopathic congenital nystagmus - Feng-wei Song; Bin-bin Chen; Zhao-hui Sun; Li-ping Wu; Su-juan Zhao; Qi Miao; Xia-jing Tang (Journal of Zhejiang University-SCIENCE B, 2013)

Tanshinone IIA and astragaloside IV promote the migration of mesenchymal stem cells by up-regulation of CXCR4 - Juan Xie; Huan Wang; Tiebing Song; Zongren Wang; Feng Li; Jing Ma; Jun Chen; Yayun Nan; Hui Yi; Wen Wang (Protoplasma, 2013)

Comparative study of the interactions between ovalbumin and three alkaloids by spectrofluorimetry - Rui-qiang Wang; Yu-jing Yin; Hua Li; Yi Wang; Juan-Juan Pu; Rui Wang; Huan-jing Dou; Chuan-jun Song; Rui-yong Wang (Molecular Biology Reports, 2013)

Successful establishment and evaluation of a new animal model for studying the hepatitis B virus YVDD mutant - Yan-Xiu Ma; Zhi-Wei Song; Xu Teng; Li-Juan Fu; Mei-Li Hao; Si-Jia Chen; Wei-Zhen Xu; Hong-Xi Gu (Archives of Virology, 2013)

Apoptosis initiation of β-ionone in SGC-7901 gastric carcinoma cancer cells via a PI3K-AKT pathway - Qian Liu; Hong-Wei Dong; Wen-Guang Sun; Ming Liu; Juan C. Ibla; Lian-Xin Liu; John W. Parry; Xiao-Hui Han; Ming-Song Li; Jia-Ren Liu (Archives of Toxicology, 2013)

Analysis of average standardized SSR allele size supports domestication of soybean along the Yellow River - Ying-hui Li; Chen Zhang; Marinus J. M. Smulders; Wei Li; Yan-song Ma; Qu Xu; Ru-zhen Chang; Li-juan Qiu (Genetic Resources and Crop Evolution, 2013)

Effects of Formaldehyde Stress on Physiological Characteristics and Gene Expression Associated with Photosynthesis in Arabidopsis thaliana - Sha-Sha Wang; Zhong-Bang Song; Zhen Sun; Jing Zhang; Yan Mei; Hong-Juan Nian; Kun-Zhi Li; Li-Mei Chen (Plant Molecular Biology Reporter, 2012)

Zinc Oxide–Montmorillonite Hybrid Influences Diarrhea, Intestinal Mucosal Integrity, and Digestive Enzyme Activity in Weaned Pigs - Caihong Hu; Juan Song; Zhaotong You; ZhaoShuang Luan; Weifen Li (Biological Trace Element Research, 2012)

Identification, fine mapping and characterization of Rht-dp, a recessive wheat dwarfing (reduced height) gene derived from Triticum polonicum - Hou-Yang Kang; Li-Juan Lin; Zhi-Jian Song; Jing-Ya Yuan; Mei-Yu Zhong; Hai-Qin Zhang; Xing Fan; Li-Na Sha; Yi Wang; Li-Li Xu; Jian Zeng; Yong-Hong Zhou (Genes & Genomics, 2012)

An efficient and high-throughput protocol for Agrobacterium-mediated transformation based on phosphomannose isomerase positive selection in Japonica rice (Oryza sativa L.) - Yongbo Duan; Chenguang Zhai; Hao Li; Juan Li; Wenqian Mei; Huaping Gui; Dahu Ni; Fengshun Song; Li Li; Wanggen Zhang; Jianbo Yang (Plant Cell Reports, 2012)

Should few retrieved oocytes be as an indication for intracytoplasmic sperm injection? - Qing-song Xi; Li-xia Zhu; Juan Hu; Li Wu; Han-wang Zhang (Journal of Zhejiang University-SCIENCE B, 2012)

Passive stretch reduces calpain activity through nitric oxide pathway in unloaded soleus muscles - Peng-Tao Xu; Quan Li; Juan–Juan Sheng; Hui Chang; Zhen Song; Zhi-Bin Yu (Molecular and Cellular Biochemistry, 2012)

Polymorphisms in luteinizing hormone receptor and hypothalamic gonadotropin-releasing hormone genes and their effects on sperm quality traits in Chinese Holstein bulls - Li-Ping Sun; Qing-Zhi Du; Ya-Pan Song; Jun-Na Yu; Shu-Juan Wang; Lei Sang; Luo-Wen Song; Yao-Min Yue; Yu-Ze Lian; Sheng-Li Zhang; Guo-Hua Hua; Shu-Jun Zhang; et al. (Molecular Biology Reports, 2012)

Conditional QTL underlying resistance to late blight in a diploid potato population - Jingcai Li; Hannele Lindqvist-Kreuze; Zhendong Tian; Jun Liu; Botao Song; Juan Landeo; Leticia Portal; Manuel Gastelo; Julio Frisancho; Laura Sanchez; Dennis Meijer; Conghua Xie; et al. (Theoretical and Applied Genetics, 2012)

Erratum to: Physiological and transcriptional analysis of the effects of formaldehyde exposure on Arabidopsis thaliana - Sha-Sha Wang; Zhong-Bang Song; Zhen Sun; Jing Zhang; Yan Mei; Hong-Juan Nian; Kun-Zhi Li; Li-Mei Chen (Acta Physiologiae Plantarum, 2012)

Physiological and transcriptional analysis of the effects of formaldehyde exposure on Arabidopsis thaliana - Sha-Sha Wang; Zhong-Bang Song; Zhen Sun; Jing Zhang; Yan Mei; Hong-Juan Nian; Kun-Zhi Li; Li-Mei Chen (Acta Physiologiae Plantarum, 2012)

Variation in the internalization of differently sized nanoparticles induces different DNA-damaging effects on a macrophage cell line - Mingyi Zhang; Juan Li; Gengmei Xing; Rui He; Wei Li; Yan Song; Haili Guo (Archives of Toxicology, 2011)

Induction of DIMBOA accumulation and systemic defense responses as a mechanism of enhanced resistance of mycorrhizal corn (Zea mays L.) to sheath blight - Yuan Yuan Song; Man Cao; Li Jun Xie; Xiao Ting Liang; Ren Sen Zeng; Yi Juan Su; Jing Hua Huang; Rui Long Wang; Shi Ming Luo (Mycorrhiza, 2011)

Dwarf apple MbDREB1 enhances plant tolerance to low temperature, drought, and salt stress via both ABA-dependent and ABA-independent pathways - Wei Yang; Xiao-Dan Liu; Xiao-Juan Chi; Chang-Ai Wu; Yan-Ze Li; Li-Li Song; Xiu-Ming Liu; Yan-Fang Wang; Fa-Wei Wang; Chuang Zhang; Yang Liu; Jun-Mei Zong; et al. (Planta, 2011)

The pentapeptide PLNPK inhibits systemic lupus erythematosus-associated renal damage - Jun-qiang Lv; Wen Zhang; Song Wang; Lin Zhao; Rui Ma; Jin-wei Hu; Li-juan Wang; Jie Meng; Chun-lei Zhou; Gang Lin; Rong Lu; Zhi Yao (Inflammation Research, 2010)

Genetic diversity and population structure of 10 Chinese indigenous egg-type duck breeds assessed by microsatellite polymorphism - Hui-Fang Li; Wei-Tao Song; Jing-Ting Shu; Kuan-Wei Chen; Wen-Qi Zhu; Wei Han; Wen-Juan Xu (Journal of Genetics, 2010)

FAK is involved in invasion and metastasis of hepatocellular carcinoma - Jing-Song Chen; Xiao-Hui Huang; Qian Wang; Xi-Lin Chen; Xin-Hui Fu; Hao-Xiang Tan; Long-Juan Zhang; Wen Li; Jiong Bi (Clinical & Experimental Metastasis, 2010)

Unexpected effect of concomitantly administered curcumin on the pharmacokinetics of talinolol in healthy Chinese volunteers - He Juan; Bernd Terhaag; Zang Cong; Zhang Bi-Kui; Zhu Rong-Hua; Wang Feng; Su Fen-Li; Song Juan; Tang Jing; Peng Wen-Xing (European Journal of Clinical Pharmacology, 2007)

Comparative analysis of telomeric restriction fragment lengths in different tissues of Ginkgo biloba trees of different age - Di Liu; Nan Qiao; Han Song; Xin Hua; Juan Du; Hai Lu; Fenglan Li (Journal of Plant Research, 2007)

A locus for autosomal dominant accessory auricular anomaly maps to 14q11.2–q12 - Yongjia Yang; Jihong Guo; Zheng Liu; Siyuan Tang; Ningdong Li; Mengrong Yang; Qiong Pang; Feiyue Fan; Juan Bu; Song Tao Yuan; Xiangjun Xiao; Yuxiang Chen; et al. (Human Genetics, 2006)

Intestinal microflora in rats with ischemia/reperfusion liver injury - Hui-chun Xing; Lan-juan Li; Kai-jin Xu; Tian Shen; Yun-bo Chen; Ji-fang Sheng; Yun-song Yu; Ya-gang Chen (Journal of Zhejiang University-SCIENCE B, 2005)

Characterization of soybean genomic features by analysis of its expressed sequence tags - Ai-Guo Tian; Jun Wang; Peng Cui; Yu-Jun Han; Hao Xu; Li-Juan Cong; Xian-Gang Huang; Xiao-Ling Wang; Yong-Zhi Jiao; Bang-Jun Wang; Yong-Jun Wang; Jin-Song Zhang; et al. (Theoretical and Applied Genetics, 2004)

The effects of DNA hypomethylating drugs on androgenesis in barley (Hordeum vulgare L.) - Wen-Ze Li; Zi-Hong Song; Bao-Tai Guo; Li-Juan Xu (In Vitro Cellular & Developmental Biology - Plant, 2001)